Silicon anode multilayer for electrochemical cells

By using a double-layer anode composition in a lithium-ion battery, using different components and structures of the first and second anode layers, the problem of degradation in battery performance caused by volume changes in the silicon anode material is solved, and higher battery capacity stability and cycle life are achieved.

CN119856292APending Publication Date: 2025-04-18SOLID POWER OPERATING INC
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202380065231.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-07-15
Filing Date
2023-07-14
Publication Date
2025-04-18

AI Technical Summary

Technical Problem

In existing lithium-ion batteries, silicon-based anode material cracks due to volume expansion and contraction during lithium ion storage, resulting in degradation in battery cell performance and ultimate failure.

Method used

A double-layer anode composition is used, wherein the first anode layer and the second anode layer each contain an anode active material, a binder, a conductive additive and a solid electrolyte material, and the two layers are in close contact by stacking pressure to maintain interface contact.

Benefits of technology

Through the double-layer anode structure, the negative impact of volume expansion and contraction on battery performance is reduced, the discharge specific capacity and capacity stability of the battery cell are improved, the internal resistance is reduced, and the cycle life of the battery is extended.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119856292A_ABST
    Figure CN119856292A_ABST
Patent Text Reader

Abstract

A negative electrode or anode having two or more layers for an electrochemical cell is provided herein. Each layer may include a different concentration of anode active material compared to a single layer anode to provide improved electrical and physical quality.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] CROSS-REFERENCE TO RELATED APPLICATIONS

[0002] This application is related to and claims priority under 35 U.S.C. §119(e) to U.S. Patent Application No. 63 / 389,701, filed on July 15, 2022, entitled “Silicon Anode Multilayer for Electrochemical Cells,” the entire contents of which are incorporated herein by reference for all purposes. Technical Field

[0003] Various embodiments described herein relate to the field of primary and secondary electrochemical cells containing solid electrolytes, electrodes and electrode materials and electrolyte materials, and corresponding methods of making and using the same. Background Art

[0004] Lithium-based rechargeable batteries widely power many forms of modern electronics and can serve as a power source for hybrid and all-electric vehicles. State-of-the-art lithium-based rechargeable batteries typically employ carbon-based anodes to store lithium ions. In these anodes, lithium ions are stored by inserting between planes of carbon atoms that make up graphite particles. Carbon-based anodes have been tailored to impart acceptable performance in modern lithium-ion batteries. However, carbon-based anodes are reaching maturity for lithium-ion storage.

[0005] An alternative to carbon-based anodes are alloy-type anodes. In alloy-type anodes, instead of being embedded between carbon sheets in graphite particles, the lithium ions are alloyed with the active anode material. These materials can have a lithium-ion storage capacity ten times (10x) greater than that of graphite anodes. Common alloy-type anodes include silicon, tin, and aluminum, as well as more exotic materials such as germanium and gold. These alloy materials have their own advantages and disadvantages such as cost, specific capacity, processability, and voltage loss.

[0006] One of the challenges facing these systems is the volume changes associated with alloying the lithium and active materials. For example, some systems may experience volume changes approaching 400%. The volume changes can cause difficulties at both the macro and micro levels. At the macro level, the battery pack may have to accommodate swollen battery cells, while at the micro level, the continued expansion and contraction of the active area may cause cracking. The particles in the active area may then lose electrical connection to their surrounding matrix and may also experience undesirable side reactions between the fresh surface of the particles and the battery electrolyte.

[0007] Silicon (Si) is an example of an alloy-type anode material that can theoretically store more than ten times the amount of lithium ions as graphite, with modest voltage loss, and is abundant and cheap in bulk form. Unfortunately, efforts to use silicon in anodes have been frustrated by the large (e.g., 400%) volume changes of silicon-lithium alloys in conventional liquid electrolyte lithium-ion cells. As the material expands and contracts, cracking occurs, and the fresh surfaces of the exposed cracks react to form new solid electrolyte interfaces, consuming the supply of electrolyte and lithium in the cell. As a result, the cell loses a portion of its capacity during each cycle and may eventually fail after a certain number of cycles.

[0008] There are not many solutions to the volume expansion problem. The most common solution is to simply reduce the amount of active material in the anode, which results in less volume expansion and contraction. However, this also results in poorer performance of the electrochemical cell, including reduced capacity of the cell. Liquid electrolytes have also been used to maintain contact between the anode and the electrolyte, but solid electrolytes are generally safer than liquid electrolytes and have higher thermal stability.

[0009] What is needed is an anode that provides improved cell performance and maintains interfacial contact with the electrolyte layer. Summary of the invention

[0010] Provided herein is an anode composition. The composition comprises a first anode layer in operative contact with a second anode layer. The first anode layer and the second anode layer each comprise an anode active material, a binder, a conductive additive, and optionally a solid electrolyte material. In some embodiments, the second anode layer comprises a solid electrolyte material. The weight percentage amount of the anode active material, binder, conductive additive, and / or solid electrolyte material in the first anode layer is different from the amount in the second anode layer. In an exemplary embodiment, the first anode layer is in direct contact with the second anode layer.

[0011] In some embodiments, the anode active material is present in the first anode layer in an amount greater than or equal to about 50% by weight of the first anode layer. In some embodiments, the anode active material is present in the second anode layer in an amount from about 20% to about 70% by weight of the second anode layer.

[0012] In some embodiments, the anode active material of the first anode layer is an inorganic material. In some aspects, the inorganic material is selected from the group consisting of silicon, silicon alloys, tin, tin alloys, germanium, germanium alloys, and combinations thereof. In exemplary embodiments, the inorganic material is silicon, silicon alloys, or combinations thereof. In further exemplary embodiments, the particle size of the silicon or silicon alloy is less than about 1 micron.

[0013] In some embodiments, the anode active material of the second anode layer is an inorganic material. In some aspects, the inorganic material is selected from the group consisting of silicon, silicon alloys, tin, tin alloys, germanium, germanium alloys, and combinations thereof. In exemplary embodiments, the inorganic material is silicon, silicon alloys, or combinations thereof. In further exemplary embodiments, the particle size of the silicon or silicon alloy is about 1 micron. In still further exemplary embodiments, the anode active material in the first anode layer is the same as the anode active material in the second anode layer. In even further exemplary embodiments, the anode active material in the first anode layer is different from the anode active material in the second anode layer.

[0014] In some embodiments, the conductive additive of the first anode layer comprises a carbon-based conductive additive. In some aspects, the carbon-based conductive additive is selected from the group consisting of graphite, graphene, carbon black, carbon nanotubes, carbon nanowires, vapor-grown carbon fibers, activated carbon, and combinations thereof.

[0015] In some embodiments, the conductive additive of the second anode layer comprises a carbon-based conductive additive. In some aspects, the carbon-based conductive additive is selected from the group consisting of graphite, graphene, carbon black, carbon nanotubes, carbon nanowires, vapor-grown carbon fibers, activated carbon, and combinations thereof.

[0016] In some embodiments, the second anode layer further comprises an adhesion promoter. In some aspects, the adhesion promoter comprises a hydrocarbon resin.

[0017] In some embodiments, the second layer further comprises a plasticizer. In some aspects, the plasticizer is dioctyl phthalate, dibutyl sebacate, mineral oil, or a combination thereof.

[0018] In some embodiments, the solid electrolyte material of the first layer is a sulfide electrolyte, an oxide electrolyte, an oxysulfide electrolyte, or a halide electrolyte. In some aspects, the particle size of the solid electrolyte material of the first layer is about 1 micron. In some embodiments, the first anode layer substantially does not contain solid electrolyte material, such as about 5 wt % or less of the first anode layer or about 1 wt % or less of the first anode layer. In some aspects, the first anode layer may be free of solid electrolyte material.

[0019] In some embodiments, the solid electrolyte material of the second layer is a sulfide electrolyte, an oxide electrolyte, an oxysulfide electrolyte, or a halide electrolyte. In some aspects, the particle size of the solid electrolyte material of the second layer is about 1 micron.

[0020] In some embodiments, the thickness of the first anode layer is about 70 microns before densification. In some further embodiments, the thickness of the second anode layer is about 50 microns before densification. In some aspects, the thickness of the first anode layer is about 40% greater than the thickness of the second anode layer.

[0021] In some embodiments, a stacking pressure of about 1500 psi or less is applied to the composition. In some embodiments, the first anode layer comprises vertical cracks. In an exemplary embodiment, the first anode layer comprises Figure 2 In some embodiments, the first anode layer comprises vertical cracks, but the second anode layer does not comprise vertical cracks. In some exemplary embodiments, the second anode layer does not exhibit cracking after the first battery cell cycle.

[0022] In some embodiments, the porosity of the first anode layer is about 25% to about 50%. In some further embodiments, the porosity of the second anode layer is about 10% to about 50%.

[0023] In some preferred embodiments, the anode active material comprises silicon in an amount of about 50% to 98% by weight of the first anode layer, and wherein the anode active material comprises silicon in an amount of about 20% to about 50% by weight of the second anode layer. In some aspects, the anode active material comprises silicon in an amount of about 50% to about 70% by weight of the first anode layer, or more preferably about 60% to about 70% by weight of the first anode layer. In still other aspects, the anode active material comprises silicon in an amount of about 20% to about 40% by weight of the second anode layer, or more preferably about 30% by weight of the second anode layer.

[0024] In some embodiments, the composition contacts a current collector. In some embodiments, the composition contacts a separator layer.

[0025] In some embodiments, the composition comprises a third anode layer. The third anode layer comprises an anode active material, a binder, a conductive additive, and a solid electrolyte material. The amount of the anode active material, the binder, the conductive additive, and / or the solid electrolyte material in the third anode layer may be different from the amount in the first anode layer and the second anode layer.

[0026] Further provided herein is a composition comprising a double-layer anode. The double-layer anode comprises a first anode layer and a second anode layer. The first anode layer comprises a first anode active material, wherein the first anode active material is present in the first layer in an amount greater than or equal to about 50% by weight of the first layer; a first binder, a first conductive additive; and optionally a first solid electrolyte material. The second anode layer comprises a second anode active material, wherein the second anode active material is present in the second layer in an amount from about 20% by weight to about 50% by weight of the second layer; a second binder; a second conductive additive; and a second solid electrolyte material. In some exemplary embodiments, the first anode active material is the same as the second anode active material. In some further exemplary embodiments, the first anode active material is different from the second anode active material.

[0027] In some embodiments, the first anode active material is an inorganic material. In some aspects, the inorganic material is selected from the group consisting of silicon, silicon alloys, tin, tin alloys, germanium, germanium alloys, and combinations thereof. In preferred embodiments, the inorganic material is silicon, silicon alloys, or combinations thereof. In further preferred embodiments, the particle size of the silicon or silicon alloy is less than about 1 micron.

[0028] In some embodiments, the second anode active material is an inorganic material. In some aspects, the inorganic material is selected from the group consisting of silicon, silicon alloys, tin, tin alloys, germanium, germanium alloys, and combinations thereof. In a preferred embodiment, the inorganic material is silicon, silicon alloys, or combinations thereof. In another preferred embodiment, the particle size of the silicon or silicon alloy is about 1 micron.

[0029] In some embodiments, the first conductive additive comprises a carbon-based conductive additive. In some aspects, the carbon-based conductive additive is selected from the group consisting of graphite, graphene, carbon black, carbon nanotubes, carbon nanowires, vapor-grown carbon fibers, activated carbon, and combinations thereof.

[0030] In some embodiments, the second conductive additive comprises a carbon-based conductive additive. In some aspects, the carbon-based conductive additive is selected from the group consisting of graphite, graphene, carbon black, carbon nanotubes, carbon nanowires, vapor-grown carbon fibers, activated carbon, and combinations thereof.

[0031] In some embodiments, the second anode layer further comprises an adhesion promoter. In some aspects, the adhesion promoter comprises a hydrocarbon resin.

[0032] In some embodiments, wherein the second anode layer further comprises a plasticizer. In some aspects, the plasticizer is dioctyl phthalate, dibutyl sebacate, mineral oil, or a combination thereof.

[0033] In some embodiments, the first solid electrolyte material is a sulfide electrolyte, an oxide electrolyte, an oxysulfide electrolyte, or a halide electrolyte. In some aspects, the particle size of the first solid electrolyte material is about 1 micron. In some embodiments, the second solid electrolyte material is a sulfide electrolyte, an oxide electrolyte, an oxysulfide electrolyte, or a halide electrolyte. In some aspects, the particle size of the second solid electrolyte material is about 1 micron. In some embodiments, the first anode layer is substantially free of solid electrolyte material, such as about 5 weight % or less of the first anode layer or about 1 weight % or less of the first anode layer. In some aspects, the first anode layer may be free of solid electrolyte material.

[0034] In some embodiments, the thickness of the first anode layer is about 70 microns before densification. In some embodiments, the thickness of the second anode layer is about 50 microns before densification. In an exemplary embodiment, the thickness of the first anode layer is about 40% greater than the thickness of the second anode layer.

[0035] In some embodiments, a stacking pressure of about 1500 psi or less is applied to the composition. In some embodiments, the second anode layer exhibits no cracking after the first cell cycle.

[0036] In some embodiments, the porosity of the first anode layer is about 25% to about 50%. In some embodiments, the porosity of the second layer is about 10% to about 50%.

[0037] In an exemplary embodiment, the first anode active material comprises silicon in an amount of about 50% to 98% by weight of the first anode layer, and wherein the second anode active material comprises silicon in an amount of about 20% to about 50% by weight of the second anode layer. In a preferred embodiment, the first anode active material comprises silicon in an amount of about 50% to about 70% by weight of the first anode layer, or more preferably about 60% to about 70% by weight of the first anode layer. In a preferred embodiment, the second anode active material comprises silicon in an amount of about 20% to about 40% by weight of the second anode layer, or more preferably about 30% by weight of the second anode layer.

[0038] In some embodiments, the anode bilayer contacts the current collector. In some embodiments, the anode bilayer contacts the separator layer.

[0039] In some embodiments, the first anode layer comprises vertical cracks. In some other embodiments, the first anode layer comprises vertical cracks, but the second anode layer does not comprise vertical cracks. In an exemplary embodiment, the first anode layer comprises Figure 2 The vertical cracks shown.

[0040] The present invention further provides an anode composition. The solid anode composition comprises a first anode layer and a second anode layer. The first anode layer comprises an active material, the active material comprising an amount of about 60% by weight or more of silicon of the first layer, an amount of about 7% by weight or less of the first binder of the first layer, an amount of about 5% by weight or less of the first conductive additive of the first layer, and an amount of about 23% by weight or less of the first solid electrolyte material of the first layer. The second layer comprises a second anode active material, the second anode active material comprising an amount of about 30% by weight of silicon of the second layer, an amount of about 6% by weight of the second binder of the second layer, an amount of about 5% by weight of the second conductive additive of the second layer, an amount of about 45% by weight or less of the second solid electrolyte material of the second layer, an amount of about 4% by weight of the second layer of plasticizer and an amount of about 10% by weight of the second layer of viscosity enhancer.

[0041] The present invention further provides an anode composition. The solid anode composition comprises a first anode layer and a second anode layer. The first anode layer comprises an active material, the active material comprising an amount of about 60% by weight or more of silicon of the first layer, an amount of about 7% by weight or less of the first binder of the first layer, an amount of about 5% by weight or less of the first conductive additive of the first layer, and an amount of about 23% by weight or less of the first solid electrolyte material of the first layer. The second layer comprises a second anode active material, the second anode active material comprising an amount of about 30% by weight of silicon of the second layer, an amount of about 6% by weight of the second binder of the second layer, an amount of about 5% by weight of the second conductive additive of the second layer, an amount of about 45% by weight or less of the second solid electrolyte material of the second layer, an amount of about 4% by weight of the second layer of plasticizer and an amount of about 10% by weight of the second layer of viscosity enhancer.

[0042] The present invention further provides an anode composition. The anode composition comprises a first anode layer and a second anode layer. The first anode layer comprises an anode active material in an amount of about 60% by weight or more of the first layer, a first binder in an amount of about 0% by weight to about 20% by weight of the first layer, and a first solid electrolyte material in an amount of about 20% by weight to about 30% by weight of the first layer. The second layer comprises a second anode active material in an amount of about 20% by weight to about 70% by weight of the second layer, a second binder in an amount of about 10% by weight or less of the second layer, and a second solid electrolyte material in an amount of about 45% by weight or less of the second layer.

[0043] Further provided herein is an electrochemical cell comprising a double-layer anode, a separator layer, and a cathode layer of the present disclosure. The electrolyte within the layers of the electrochemical cell may be solid, semi-solid (e.g., gel), and / or liquid. In a particular embodiment, the anode layer may be a solid anode layer.

[0044] In some embodiments, the electrochemical cell further comprises a first current collector disposed adjacent to the bilayer anode. In some aspects, the first current collector comprises copper, nickel, or stainless steel.

[0045] In some embodiments, the electrochemical cell has a higher specific discharge capacity than an electrochemical cell comprising a single-layer anode. In some embodiments, the discharge capacity of the cell is stable over more cycles than an electrochemical cell comprising a single-layer anode. In an exemplary embodiment, the discharge capacity of the cell is stable for at least 100 cycles.

[0046] In some embodiments, the electrochemical cell has a lower internal resistance compared to an electrochemical cell comprising a single layer anode.

[0047] In some embodiments, the bilayer anode does not separate from the separator layer when the electrochemical cell is cycled at a stack pressure of less than 1500 psi.

[0048] In some embodiments, the double layer anode has better surface area contact with the separator layer than an electrochemical cell with a single layer anode. In some embodiments, the surface area contact of the double layer anode and the separator layer is determined by SEM imaging. In some embodiments, there is less void space between the double layer anode and the separator layer than an electrochemical cell with a single layer anode.

[0049] Further provided herein is a method for preparing a double-layer anode composition. The method comprises a) forming a first anode slurry by mixing an anode active material, at least one solid electrolyte material, at least one binder material and a solvent; b) forming a second anode layer slurry by mixing an anode active material, at least one solid electrolyte material, at least one binder material, optionally at least one viscosity enhancer, optionally at least one plasticizer and a solvent; c) casting the first anode layer slurry onto a substrate; d) casting the second anode layer slurry onto the first anode layer slurry; and e) drying the first anode layer slurry and the second anode layer slurry to form an anode double layer.

[0050] Further provided herein is a method for preparing a double-layer anode composition. The method comprises a) forming a first anode layer slurry by mixing an anode active material, optionally at least one solid electrolyte material, at least one binder material, and a solvent; b) forming a second anode layer slurry by mixing an anode active material, at least one solid electrolyte material, at least one binder material, optionally at least one viscosity enhancer, optionally at least one plasticizer, and a solvent; c) casting the first anode layer slurry onto a substrate and drying the first anode layer slurry; and d) casting the second anode layer slurry onto the first anode layer slurry and drying the second anode layer slurry.

[0051] Further provided herein is an electrochemical cell comprising a double-layer anode, a separator layer, and a cathode layer of the present disclosure. BRIEF DESCRIPTION OF THE DRAWINGS

[0052] The present disclosure can be understood by referring to the following detailed description in conjunction with the accompanying drawings which are briefly described below.It should be noted that for purposes of clarity of illustration, some elements in the drawings may not be drawn to scale.

[0053] Figure 1 An electrochemical cell comprising a bilayer anode of the present disclosure is shown. The cell was cycled at 29°C with a stack pressure of about 300 psi.

[0054] Figure 2 An electrochemical cell comprising a double-layer anode of the present disclosure is shown.

[0055] Figures 3A-3D Cycling data for an electrochemical cell comprising a single layer anode and an electrochemical cell comprising a double layer anode of the present disclosure are shown. Figure 3A The cell capacity retention after about 120 cycles is shown. Figure 3B The discharge capacity (mAh) after about 120 cycles is shown. Figure 3C The internal resistance (Ohms) after about 120 cycles is shown. Figure 3D The efficiency after about 120 cycles is shown.

[0056] Figures 4A-4C Shown are cycling data for an electrochemical cell comprising a single layer anode shown as open circles (O) and a dual layer anode of the present disclosure shown as filled circles (·). Figure 4A The specific discharge capacity (mAh / g) after about 250 cycles is shown. Figure 4B The discharge capacity (mAh) after about 250 cycles is shown. Figure 4C The internal resistance (Ohms) after about 250 cycles is shown.

[0057] Figures 5A-5D Cycling data for an electrochemical cell of the present disclosure containing a tackifier and a plasticizer, shown as solid circles (·), is shown compared to a similar electrochemical cell without the plasticizer and tackifier, shown as open circles (○). Figure 5A The specific discharge capacity (mAh / g) after about 120 cycles is shown. Figure 5B The discharge capacity (mAh) after about 120 cycles is shown. Figure 5C The internal resistance (Ohms) after about 120 cycles is shown. Figure 5D The efficiency after about 120 cycles is shown.

[0058] Figures 6A-6D Cycling data for an electrochemical cell of the present disclosure containing a three-layer anode is shown. Fig. 6A The specific discharge capacity (mAh / g) after about 40 cycles is shown. Figure 6B The discharge capacity (mAh) after about 40 cycles is shown. Figure 6C The internal resistance (Ohms) after about 40 cycles is shown. Fig.6D The efficiency after about 40 cycles is shown.

[0059] Figure 7 The cell capacity retention is shown for electrochemical cells of the present disclosure including a double layer anode without a solid electrolyte material in the first anode layer and a cell having a single layer anode. DETAILED DESCRIPTION

[0060] In the following description, specific details are provided to give a thorough understanding of the various embodiments of the present disclosure. Upon reading and understanding the specification, claims, and drawings herein, those skilled in the art will understand that some embodiments may be practiced without being bound by some of the specific details set forth herein. In addition, to avoid obscuring the present disclosure, some well-known methods, processes, devices, and systems used in the various embodiments described herein are not disclosed in detail.

[0061] Provided herein is an anode bilayer comprising a first anode layer in operative contact with a second anode layer. The first anode layer and the second anode layer each independently comprise an anode active material, a binder, a conductive additive, and optionally a solid electrolyte material. The amount of anode active material, binder, conductive additive, and / or solid electrolyte material in the first anode layer is different from the amount of anode active material, binder, conductive additive, and / or solid electrolyte material in the second anode layer.

[0062] Also provided herein is a composition comprising an anode bilayer, the anode bilayer comprising a first layer and a second layer. The first layer includes a first anode active material, a first binder, a first conductive additive and optionally a first solid electrolyte material. The amount of the first anode active material present in the first layer is greater than or equal to about 50% by weight of the first layer. The second layer includes a second anode active material, a second binder, a second conductive additive and a second solid electrolyte material. The amount of the second anode active material present in the second layer is greater than or equal to about 50% by weight of the second layer. The first anode active material and the second anode active material may be the same anode active material, or the first anode active material and the second anode active material may be different. The first binder and the second binder may be the same binder, or the first binder and the second binder may be different. The first conductive additive and the second conductive additive may be the same conductive additive, or the first conductive additive and the second conductive additive may be different. The first solid electrolyte material and the second electrolyte material may be the same solid electrolyte material, or the first solid electrolyte material and the second electrolyte material may be different.

[0063] It should be understood that within the meaning of the present disclosure, the phrase "first anode active material" may refer to a single anode active material or more than one anode active material. That is, the label "first" or "second" should not be interpreted as limiting the anode active material involved to a single species. In addition, phrases such as "anode active material" or "anode active material" should be interpreted as also referring to the first anode active material and / or the second anode active material. Similarly, references to "anode layer" should be interpreted as including references to the first anode layer and / or the second anode layer.

[0064] Figure 1 An electrochemical cell including an anode bilayer of the present disclosure is shown. A first anode layer 100 can contact an anode current collector 110. A second anode layer 102 can contact a separator layer 104 (also referred to as an electrolyte layer). The first anode layer 100 and the second anode layer 102 can be in direct contact with each other. The separator layer 104 can contact a cathode layer 106. The cathode layer 106 can contact a cathode current collector 108.

[0065] Each anode layer comprises an anode active material. The anode active material is preferably an inorganic material. The anode active material may comprise one or more inorganic materials, such as silicon (Si), a silicon alloy (e.g., Li x Si), tin (Sn), tin alloy, germanium (Ge), germanium alloy, graphite, Li 4 Ti 5 O 12 (LTO) or other known anode active materials and combinations thereof. In a preferred embodiment, the anode active material comprises silicon.

[0066] The average particle size of the silicon or silicon alloy in the first anode layer can be less than about 1 micron. As used herein, "silicon" refers to silicon metal or its alloys, unless otherwise specified. The average particle size of silicon (i.e., D 50 ) can be described using methods well known in the art. In some aspects, the average particle size of silicon can be less than 500nm, less than 450nm, less than 400nm, less than 350nm, less than 300nm, less than 250nm, less than 200nm, less than 150nm or less than 100nm. In some instances, the average particle size of silicon is about 100nm. In an exemplary embodiment, the average particle size of silicon is about 50nm to about 150nm. In some other aspects, the average particle size of silicon or silicon alloy can be about 50nm to about 100nm, about 100nm to about 150nm, about 150nm to about 200nm, about 200nm to about 300nm, about 300nm to about 400nm, about 400nm to about 500nm, about 500nm to about 600nm, about 600nm to about 700nm, about 700nm to about 800nm, about 800nm ​​to about 900nm or about 900nm to about 1000nm. In still further aspects, the average particle size of the silicon or silicon alloy can be from about 50 nm to about 150 nm, from about 50 nm to about 200 nm, from about 50 nm to about 300 nm, from about 50 nm to about 400 nm, from about 50 nm to about 500 nm, from about 50 nm to about 600 nm, from about 50 nm to about 700 nm, from about 50 nm to about 800 nm, from about 50 nm to about 900 nm, or from about 50 nm to about 1000 nm.

[0067] The average particle size of the silicon or silicon alloy in the first anode layer can be about 1 micron. In some aspects, the average particle size of the silicon or silicon alloy can be about 50nm to about 100nm, about 100nm to about 150nm, about 150nm to about 200nm, about 200nm to about 300nm, about 300nm to about 400nm, about 400nm to about 500nm, about 500nm to about 600nm, about 600nm to about 700nm, about 700nm to about 800nm, about 800nm ​​to about 900nm, about 900nm to about 1 micron, about 1 micron to about 2 microns, about 2 microns to about 3 microns, about 3 microns to about 4 microns or about 4 microns to about 5 microns. In still further aspects, the average particle size of the silicon or silicon alloy can be from about 50 nm to about 150 nm, from about 50 nm to about 200 nm, from about 50 nm to about 300 nm, from about 50 nm to about 400 nm, from about 50 nm to about 500 nm, from about 50 nm to about 600 nm, from about 50 nm to about 700 nm, from about 50 nm to about 800 nm, from about 50 nm to about 900 nm, from about 50 nm to about 1 micrometer, from about 50 nm to about 2 micrometers, from about 50 nm to about 3 micrometers ... From about 50 nm to about 4 microns, from about 50 nm to about 5 microns, from about 100 nm to about 5 microns, from about 150 nm to about 5 microns, from about 200 nm to about 5 microns, from about 300 nm to about 5 microns, from about 400 nm to about 5 microns, from about 500 nm to about 5 microns, from about 600 nm to about 5 microns, from about 700 nm to about 5 microns, from about 800 nm to about 5 microns, from about 900 nm to about 5 microns, from about 1 micron to about 5 microns, from about 2 microns to about 5 microns, or from about 3 microns to about 5 microns.

[0068] The average grain size of the silicon or silicon alloy in the second anode layer may be less than about 1 micron. 50) can be described using methods well known in the art. In some aspects, the average particle size of silicon can be less than 500nm, less than 450nm, less than 400nm, less than 350nm, less than 300nm, less than 250nm, less than 200nm, less than 150nm or less than 100nm. In some instances, the average particle size of silicon is about 100nm. In an exemplary embodiment, the average particle size of silicon is about 50nm to about 150nm. In some other aspects, the average particle size of silicon or silicon alloy can be about 50nm to about 100nm, about 100nm to about 150nm, about 150nm to about 200nm, about 200nm to about 300nm, about 300nm to about 400nm, about 400nm to about 500nm, about 500nm to about 600nm, about 600nm to about 700nm, about 700nm to about 800nm, about 800nm ​​to about 900nm or about 900nm to about 1000nm. In still further aspects, the average particle size of the silicon or silicon alloy can be from about 50 nm to about 150 nm, from about 50 nm to about 200 nm, from about 50 nm to about 300 nm, from about 50 nm to about 400 nm, from about 50 nm to about 500 nm, from about 50 nm to about 600 nm, from about 50 nm to about 700 nm, from about 50 nm to about 800 nm, from about 50 nm to about 900 nm, or from about 50 nm to about 1000 nm.

[0069] The average particle size of the silicon or silicon alloy in the second anode layer can be about 1 micron. In some aspects, the average particle size of the silicon or silicon alloy can be about 50nm to about 100nm, about 100nm to about 150nm, about 150nm to about 200nm, about 200nm to about 300nm, about 300nm to about 400nm, about 400nm to about 500nm, about 500nm to about 600nm, about 600nm to about 700nm, about 700nm to about 800nm, about 800nm ​​to about 900nm, about 900nm to about 1 micron, about 1 micron to about 2 microns, about 2 microns to about 3 microns, about 3 microns to about 4 microns or about 4 microns to about 5 microns. In still further aspects, the average particle size of the silicon or silicon alloy can be from about 50 nm to about 150 nm, from about 50 nm to about 200 nm, from about 50 nm to about 300 nm, from about 50 nm to about 400 nm, from about 50 nm to about 500 nm, from about 50 nm to about 600 nm, from about 50 nm to about 700 nm, from about 50 nm to about 800 nm, from about 50 nm to about 900 nm, from about 50 nm to about 1 micrometer, from about 50 nm to about 2 micrometers, from about 50 nm to about 3 micrometers ... From about 50 nm to about 4 microns, from about 50 nm to about 5 microns, from about 100 nm to about 5 microns, from about 150 nm to about 5 microns, from about 200 nm to about 5 microns, from about 300 nm to about 5 microns, from about 400 nm to about 5 microns, from about 500 nm to about 5 microns, from about 600 nm to about 5 microns, from about 700 nm to about 5 microns, from about 800 nm to about 5 microns, from about 900 nm to about 5 microns, from about 1 micron to about 5 microns, from about 2 microns to about 5 microns, or from about 3 microns to about 5 microns.

[0070] Anode active material can be present in the first anode layer in an amount greater than or equal to about 40 wt %. In some aspects, anode active material can be present in the first anode layer in an amount of about 35 wt % to about 85 wt %, about 40 wt % to about 85 wt %, about 40 wt % to about 80 wt %, about 40 wt % to about 75 wt %, about 40 wt % to about 70 wt %, about 40 wt % to about 65 wt %, about 40 wt % to about 60 wt %, about 40 wt % to about 55 wt % or about 40 wt % to about 50 wt %. In some other aspects, anode active material can be present in the first anode layer in an amount greater than or equal to about 50 wt %. In some instances, anode active material is present in the first anode layer in an amount of about 50 wt % to about 60 wt %. In some additional aspects, the anode active material can be present in the first anode layer in an amount of about 40 wt % to about 50 wt %, about 50 wt % to about 60 wt %, about 60 wt % to about 70 wt %, about 70 wt % to about 80 wt %, about 80 wt % to about 85 wt %.

[0071] The anode active material may be present in the second anode layer in an amount of about 20 wt % to about 70 wt % of the second anode layer. In some aspects, the anode active material can be present in the second anode layer in an amount of about 20 wt % to about 70 wt %, about 20 wt % to about 65 wt %, about 20 wt % to about 60 wt %, about 20 wt % to about 55 wt %, about 20 wt % to about 50 wt %, about 20 wt % to about 45 wt %, about 20 wt % to about 40 wt %, about 20 wt % to about 35 wt %, about 20 wt % to about 30 wt %, about 25 wt % to about 50 wt %, about 25 wt % to about 45 wt %, about 25 wt % to about 40 wt %, about 25 wt % to about 35 wt %, about 30 wt % to about 50 wt %, about 30 wt % to about 45 wt %, about 30 wt % to about 40 wt %, about 35 wt % to about 50 wt %, about 35 wt % to about 45 wt %, or about 40 wt % to about 50 wt %. In some additional aspects, the anode active material can be present in the second anode layer in an amount of about 20 wt % to about 25 wt %, about 25 wt % to about 30 wt %, about 30 wt % to about 35 wt %, about 35 wt % to about 40 wt %, about 40 wt % to about 45 wt %, or about 45 wt % to about 50 wt %.

[0072] In some embodiments, the composition comprises a third anode layer.The third anode layer can be disposed adjacent to the second anode layer and, if present, adjacent to the separator layer.

[0073] Anode active material can be present in the third anode layer with an amount of about 10 wt % to about 90 wt % of the third layer. The third anode layer can be adjacent to the second anode layer and (if present) adjacent to the separator layer. In some aspects, anode active material can be present in the third anode layer with the following amount: about 10 wt % to about 20 wt %, about 10 wt % to about 30 wt %, about 10 wt % to about 40 wt %, about 10 wt % to about 50 wt %, about 10 wt % to about 60 wt %, about 10 wt % to about 70 wt %, about 10 wt % to about 80 wt %, about 20 wt % to about 90 wt %, about 30 wt % to about 90 wt %, about 40 wt % to about 90 wt %, about 50 wt % to about 90 wt %, about 60 wt % to about 90 wt %, about 70 wt % to about 90 wt % or about 80 wt % to about 90 wt %.

[0074] In some embodiments, the composition may further comprise a fourth anode layer, a fifth anode layer, a sixth anode layer, ... or an nth layer.

[0075] In another embodiment, the anode active material in any anode layer (including the first anode layer, the second anode layer, the third anode layer, ... and the nth anode layer) may be present in an amount of about 5 wt % to about 99 wt % of the anode layer. For example, the anode active material can be present in any anode layer in an amount of about 5 wt % to about 10 wt %, about 5 wt % to about 20 wt %, about 5 wt % to about 30 wt %, about 5 wt % to about 40 wt %, about 5 wt % to about 50 wt %, about 5 wt % to about 60 wt %, about 5 wt % to about 70 wt %, about 5 wt % to about 80 wt %, about 5 wt % to about 90 wt %, about 5 wt % to about 95 wt %, about 10 wt % to about 99 wt %, about 20 wt % to about 99 wt %, about 30 wt % to about 99 wt %, about 40 wt % to about 99 wt %, about 50 wt % to about 99 wt %, about 60 wt % to about 99 wt %, about 70 wt % to about 99 wt %, about 80 wt % to about 99 wt %, about 90 wt % to about 99 wt %, or about 95 wt % to about 99 wt %. In other examples, the anode active material can be present in any anode layer in an amount of about 5 wt % to about 10 wt %, about 10 wt % to about 20 wt %, about 20 wt % to about 30 wt %, about 30 wt % to about 40 wt %, about 40 wt % to about 50 wt %, about 50 wt % to about 60 wt %, about 60 wt % to about 70 wt %, about 70 wt % to about 80 wt %, about 80 wt % to about 90 wt %, about 90 wt % to about 95 wt %, or about 95 wt % to about 99 wt %.

[0076] Typically, each anode layer comprises a conductive additive. The conductive additive helps to evenly distribute the charge density throughout the anode. The conductive additive can include metal powders, fibers, filaments, or any other known materials for conducting electrons. The conductive additive can include a carbon-based conductive additive such as carbon fiber, graphite, graphene, carbon black, conductive carbon, amorphous carbon, vapor grown carbon fiber (VGCF), carbon nanotubes, carbon nanowires, activated carbon, and combinations thereof.

[0077] In some embodiments, the conductive additive may be present in the anode layer in an amount of about 0% to about 15% by weight of the anode layer. In some aspects, the conductive additive may be present in the anode layer in an amount of about 0% to about 10% by weight or about 0% to about 5% by weight of the anode layer. In some other aspects, the conductive additive may be present in the anode layer in an amount of about 0%, 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, 11%, 12%, 13%, 14% or about 15% of the anode layer. In an exemplary embodiment, the conductive additive is present in the anode layer in an amount of about 0% to about 5% by weight of the anode layer.

[0078] In some embodiments, the average particle size of the conductive additive can be about 5nm to about 100nm. In some aspects, the average particle size of the conductive additive can be about 5nm to about 10nm, about 5nm to about 20nm, about 5nm to about 30nm, about 5nm to about 40nm, about 5nm to about 50nm, about 5nm to about 60nm, about 5nm to about 70nm, about 5nm to about 80nm, about 5nm to about 90nm, about 10nm to about 100nm, about 20nm to about 100nm, about 30nm to about 100nm, about 40nm to about 100nm, about 50nm to about 100nm, about 60nm to about 100nm, about 70nm to about 100nm, about 80nm to about 100nm, about 90nm to about 100nm, about 10nm to about 50nm or about 20nm to about 40nm. In some instances, the particle size of the conductive additive can be about 30nm.

[0079] In some further embodiments, the average particle size of the conductive additive can be up to about 7 microns, including about 0.1 microns, about 0.5 microns, about 1 micron, about 1.5 microns, about 2 microns, about 2.5 microns, about 3 microns, about 3.5 microns, about 4 microns, about 4.5 microns, about 5 microns, about 5.5 microns, about 6 microns, about 6.5 microns, or about 7 microns. In a specific example, the conductive additive is graphite having an average particle size of about 6 microns.

[0080] One or both anode layers may comprise a solid electrolyte material. The solid electrolyte material and conductive additives help to evenly distribute the charge density throughout the anode. The one or more solid electrolyte materials may comprise an oxide, an oxysulfide, a sulfide, a halide, a nitride, or any other solid electrolyte known in the art. In some preferred embodiments, the one or more solid electrolyte materials may comprise a sulfide solid electrolyte material (i.e., a solid electrolyte having at least one sulfur component). In some embodiments, the one or more solid electrolytes may comprise one or more material combinations, such as Li2 S—P 2 S 5 , Li 2 S—P 2 S 5 —LiI, Li 2 S—P 2 S 5 —GeS 2 , Li₂ S —P 2 S 5 —Li 2 O, Li 2 S—P 2 S 5 —Li 2 O—LiI, Li 2 S-P 2 S 5 —LiI—LiBr, Li 2 S—SiS 2 , Li 2 S—SiS 2 —LiI, Li 2 S—SiS 2 —LiBr, Li 2 S—S—SiS 2 —LiCl, Li 2 S—S—SiS 2 —B 2 S 3 —LiI, Li 2 S—S—SiS 2 —P 2 S 5 —LiI, Li 2 S—B 2 S 3 , Li 2 S—P 2 S 5 —Z m S n (where m and n are positive numbers, and Z is Ge, Zn or Ga), Li 2 S—GeS 2 , Li 2 S—S—SiS 2 —Li 3 PO 4 and Li 2 S—S—SiS 2 —Li x MO y(where x and y are positive numbers, and M is P, Si, Ge, B, Al, Ga, or In). The halide solid electrolyte may have a Li-MX structure, M is a metal element, and X is a halogen. These can be represented by the general formula Li α M 4+ β N 3+ (1-β) X Ω Y (6-Ω) To represent, where: 0≤β≤1; 0≤Ω≤6; α=6-[(β*4)+(1-β)*3]; X and Y are halogens, such as F, Cl, Br, I; M is an element with an oxidation state of 4+, such as Ti, Zr, Hf and Rf; N is an element with an oxidation state of 3+, such as Ga, In and Tl, Sc, Y, Fe, Ru, Os, Er. Examples of halide electrolytes include Li 2 ZrCl 6 , Li 3 InCl 6 , Li 2.25 Hf 0.75 Fe 0.25 Cl 4 Br 2 .

[0081] In some embodiments, the first anode layer may be substantially free of solid electrolyte material. Without wishing to be bound by theory, it is believed that reducing the amount of solid electrolyte material in the first anode layer reduces the corrosion of the current collector (especially when the current collector comprises copper). As used herein, "substantially free of solid electrolyte" refers to that the amount of the solid electrolyte present in the first anode layer is about 5 weight % or less of the first anode layer. For example, the first anode layer substantially free of solid electrolyte material may include 5 weight % or less, 4 weight % or less, 3 weight % or less, 2 weight % or less, 1 weight % or less, 0.5 weight % or less, 0.1 weight % or less, 0.05 weight % or less or 0.01 weight % or less of solid electrolyte material of the first anode layer. In some other embodiments, the first anode layer may be free of solid electrolyte material.

[0082] In other embodiments, the anode layer may include a semisolid or liquid electrolyte.

[0083] In another embodiment, the solid electrolyte material may be one or more of the following: Li 3 PS 4 , Li 4 P 2 S 6 , Li 7 P 3 S 11 , Li 10GeP 2 S 12 、Li 10 SnP 2 S 12 。In another embodiment, the solid electrolyte can be Li 6 PS 5 Cl, Li 6 PS 5 Br, Li 6 PS 5 I or one or more of them or represented by the formula Li 7-y PS 6-y X y where "X" represents at least one halogen and / or at least one pseudohalogen, and where 0 < y ≤ 2.0, and where the halogen can be one or more of the following: F, Cl, Br, I, and the pseudohalogen can be one or more of the following: N, NH, NH 2 , NO, NO 2 , BF 4 , BH 4 , AlH 4 , CN and SCN. In yet another embodiment, the solid electrolyte material is represented by the formula Li 8-y-z P 2 S 9-y-z X y W z (where "X" and "W" represent at least one halogen and / or at least one pseudohalogen, and where 0 ≤ y ≤ 1 and 0 ≤ z ≤ 1), and where the halogen can be one or more of the following: F, Cl, Br, I, and the pseudohalogen can be one or more of the following: N, NH, NH 2 , NO, NO 2 , BF 4 , BH 4 , AlH 4 , CN and SCN.

[0084] In some aspects, the solid electrolyte material can be present in the anode layer in an amount of about 0 wt % to about 70 wt % of the anode layer; for example, the solid electrolyte can be present in the anode layer in an amount of about 0 wt % to about 10 wt %, about 0 wt % to about 20 wt %, about 0 wt % to about 30 wt %, about 0 wt % to about 40 wt %, about 0 wt % to about 50 wt %, about 0 wt % to about 60 wt %, about 10 wt % to about 70 wt %, about 20 wt % to about 70 wt %, about 30 wt % to about 70 wt %, about 40 wt % to about 70 wt %, about 50 wt % to about 70 wt %, or about 60 wt % to about 70 wt %. In some aspects, the solid electrolyte material can be present in the anode layer in an amount of about 5 wt %, 10 wt %, 15 wt %, 20 wt %, 25 wt %, 30 wt %, 35 wt %, 40 wt %, 45 wt %, 50 wt %, 55 wt %, 60 wt %, 65 wt % or about 70 wt % of the anode layer. In a preferred embodiment, the solid electrolyte material is present in an amount of about 20 wt % to about 30 wt % of the anode layer.

[0085] In some further aspects, the solid electrolyte material can be present in the anode layer in an amount of less than about 60% by weight of the anode layer; for example, the solid electrolyte material can be present in the anode layer in an amount of less than about 55% by weight of the anode layer, less than about 50% by weight of the anode layer, less than about 45% by weight of the anode layer, less than about 40% by weight of the anode layer, less than about 35% by weight of the anode layer, less than about 30% by weight of the anode layer, less than about 25% by weight of the anode layer, less than about 20% by weight of the anode layer, less than about 15% by weight of the anode layer, less than about 10% by weight of the anode layer, or less than about 5% by weight of the anode layer. In a preferred embodiment, the solid electrolyte material is present in an amount of less than about 25% by weight of the anode layer.

[0086] The average particle size of the solid electrolyte material is about 0.5 microns to about 2 microns. In some embodiments, the particle size of the solid electrolyte material can be about 0.5 microns to about 0.75 microns, about 0.75 microns to about 1 micron, about 1 micron to about 1.25 microns, about 1.25 microns to about 1.5 microns, about 1.5 microns to about 1.75 microns, or about 1.75 microns to about 2 microns. In a preferred embodiment, the particle size of the solid electrolyte material is about 1 micron.

[0087] Typically, the anode layer comprises a binder. The binder facilitates the bonding of the first anode layer to the current collector, and the bonding of the second anode layer to the first anode layer and the separator layer. When mixed with the solid electrolyte material, the binder also forms a flexible matrix. The binder further allows the anode active material and the conductive additive to be suspended in the electrolyte matrix, thereby allowing the electrode layer to maintain particle-to-particle contact when the anode active material expands and contracts.

[0088] In some embodiments, the binder may include a fluororesin containing vinylidene fluoride (VdF), hexafluoropropylene (HFP), tetrafluoroethylene (TFE) and its derivatives as structural units. In some other embodiments, the binder may include a homopolymer, such as polyvinylidene fluoride (PVdF), polyhexafluoropropylene (PHFP) and polytetrafluoroethylene (PTFE); and a binary copolymer, such as a copolymer of VdF and HFP, such as poly (vinylidene fluoride-hexafluoropropylene) copolymer (PVdF-HFP) and the like. In another embodiment, the binder may be one or more of a thermoplastic elastomer, such as but not limited to styrene-butadiene rubber (SBR), styrene-butadiene-styrene block copolymer (SBS), styrene-isoprene block copolymer (SIS), styrene-ethylene-butylene-styrene block copolymer (SEBS), polyacrylonitrile (PAN), nitrile-butylene rubber (NBR), polybutadiene, polyisoprene, poly (methacrylate) nitrile-butadiene rubber (PMMA-NBR) and the like. In other embodiments, the binder may include a cellulose binder such as carboxymethyl cellulose (CMC). In other embodiments, the binder may be one or more of styrene-based thermoplastics, such as but not limited to styrene-butadiene rubber (SBR), styrene-butadiene-styrene block copolymer (SBS), styrene-isoprene block copolymer (SIS), polystyrene (PS) or styrene-ethylene-butylene-styrene block copolymer (SEBS). In other embodiments, the binder may include one or more of the following: styrene-butadiene rubber (SBR), polyvinylidene fluoride (PVdF), carboxymethyl cellulose (CMC) or a combination thereof or a derivative thereof.

[0089] In other embodiments, the binder may be one or more of acrylic resins, such as but not limited to polymethyl (meth)acrylate, polyethyl (meth)acrylate, polyisopropyl (meth)acrylate, polyisobutyl (meth)acrylate, polybutyl (meth)acrylate, etc. In yet another embodiment, the binder may be one or more of condensation polymers, such as but not limited to polyurea, polyamide paper, polyimide, polyester, etc. In yet another embodiment, the binder may be one or more of nitrile rubbers, such as but not limited to acrylonitrile-butadiene rubber (ABR), polystyrene nitrile-butadiene rubber (PS-NBR), and mixtures thereof.

[0090] In a preferred embodiment, the binder may include a styrene block copolymer or a styrene-based thermoplastic. In some aspects, the binder may be present in the anode layer in an amount of about 0% to about 20% by weight of the anode layer; for example, the binder may be present in the anode layer in an amount of about 0% to about 5%, about 0% to about 10%, about 0% to about 15%, about 5% to about 20%, about 10% to about 20%, or about 15% to about 20%. In an exemplary embodiment, the binder is present in the anode layer in an amount of about 4% to about 5% by weight.

[0091] The anode layer may include a tackifier. The tackifier increases the viscosity of the anode layer, i.e., how quickly an adhesive bond is formed. Typically, the tackifier may include a hydrocarbon resin, such as a hydrogenated aromatic resin, an aromatic resin, a terpene resin, a modified terpene resin, an aliphatic resin, an alicyclic resin, a hydrogenated hydrocarbon resin, and a combination thereof. Such resins and methods for obtaining and preparing them are well known in the art. Preferably, the tackifier and the binder are miscible; i.e., have similar solubility parameters. Without wishing to be bound by theory, when the tackifier and the binder are miscible, the mixture will have a lower modulus and a higher glass transition temperature than an immiscible binder and tackifier. In a preferred embodiment, the tackifier is a hydrogenated aromatic resin. In a preferred embodiment, only the second anode layer includes a tackifier; i.e., there is no tackifier in the first anode layer.

[0092] The softening point of the tackifier may be about 20° C. to about 150° C. The molecular weight of the tackifier may be about 300 g / mol to about 10,000 g / mol. The density of the tackifier may be about 0.75 kg / L to about 1.25 kg / L. The glass transition temperature of the tackifier may be about -30° C. to about 150° C.

[0093] The adhesion promoter may be present in an amount of about 0% to about 15% by weight of the anode layer. In some aspects, the adhesion promoter may be present in an amount of about 0% to about 5% by weight of the anode layer, about 0% to about 10% by weight of the anode layer, about 5% to about 10% by weight of the anode layer, or about 10% to about 15% by weight of the anode layer. In an exemplary embodiment, the adhesion promoter is present in an amount of about 10% by weight of the anode layer.

[0094] The anode layer may comprise a plasticizer. The plasticizer increases the flexibility of the anode layer, thereby making it less susceptible to damage and cracking during volume expansion and contraction. The plasticizer may comprise phthalates, succinates, adipic acid esters and other esters. Phthalate may comprise dimethyl phthalate, diethyl phthalate, dipropyl phthalate, dibutyl phthalate, dipentyl phthalate, dihexyl phthalate, dioctyl phthalate, dinonyl phthalate, didecyl phthalate, diundecyl phthalate, didodecyl phthalate and other phthalates and isomers or derivatives thereof. Sebacate can include dimethyl sebacate, diethyl sebacate, dipropyl sebacate, dibutyl sebacate, dipentyl sebacate, dihexyl sebacate, diheptyl sebacate, dioctyl sebacate, dinonyl sebacate, didecyl sebacate, diundecyl sebacate, didodecyl sebacate and other sebacate and its isomer or derivative.Adipate can include dimethyl adipate, diethyl adipate, dipropyl adipate, dibutyl adipate, dipentyl adipate, dihexyl adipate, diheptyl adipate, dioctyl adipate, dinonyl adipate, didecyl sebacate, diundecyl sebacate, didodecyl sebacate and other adipate and its isomer or derivative.In a particular embodiment, plasticizer can include dioctyl phthalate, dibutyl sebacate, mineral oil or other plasticizer known in the art or its combination. In a preferred embodiment, only the second anode layer comprises a plasticizer; ie there is no plasticizer in the first anode layer.

[0095] Plasticizer can be present in the anode layer with an amount of about 0 % by weight to about 8 % by weight of anode layer. In some aspects, plasticizer can be present in the anode layer with an amount of about 0 % by weight to about 2 % by weight of anode layer, about 0 % by weight to about 4 % by weight of anode layer, about 0 % by weight to about 6 % by weight of anode layer, about 2 % by weight to about 4 % by weight of anode layer, about 2 % by weight to about 6 % by weight of anode layer, about 2 % by weight to about 8 % by weight of anode layer, about 4 % by weight to about 6 % by weight of anode layer, about 4 % by weight to about 6 % by weight of anode layer, about 4 % by weight to about 8 % by weight of anode layer or about 6 % by weight to about 8 % by weight of anode layer. In an exemplary embodiment, plasticizer is present in the anode layer with an amount of about 4 % by weight of anode layer.

[0096] The anode layer composition may be densified using densification methods known to those of ordinary skill in the art, including calendaring, linear pressing, and the like.

[0097] In some aspects, before densification and before drying, the thickness of the first anode layer can be about 50 microns to about 60 microns, about 50 microns to about 70 microns, about 50 microns to about 80 microns, about 50 microns to about 90 microns, about 60 microns to about 70 microns, about 60 microns to about 80 microns, about 60 microns to about 90 microns, about 60 microns to about 100 microns, about 70 microns to about 80 microns, about 70 microns to about 90 microns, about 70 microns to about 100 microns, about 80 microns to about 90 microns, about 80 microns to about 100 microns, or about 90 microns to about 100 microns. In a preferred embodiment, before densification and before drying, the thickness of the composition can be about 70 microns.

[0098] Before densification and after drying, the thickness of the first anode layer can be about 15 microns to about 50 microns. In some aspects, before densification and after drying, the thickness of the first anode layer can be about 15 microns to about 20 microns, about 20 microns to about 30 microns, about 30 microns to about 40 microns, about 40 microns to about 50 microns, about 15 microns to about 30 microns, about 15 microns to about 40 microns, about 20 microns to about 50 microns, about 30 microns to about 50 microns, or about 40 microns to about 50 microns.

[0099] Before densification and before drying, the thickness of the second anode layer can be about 20 microns to about 70 microns. In certain embodiments, before densification and before drying, the thickness of the second anode layer can be about 20 microns to about 30 microns, about 20 microns to about 40 microns, about 20 microns to about 50 microns, about 20 microns to about 60 microns, about 30 microns to about 40 microns, about 30 microns to about 50 microns, about 30 microns to about 60 microns, about 30 microns to about 70 microns, about 40 microns to about 50 microns, about 40 microns to about 60 microns, about 40 microns to about 70 microns, about 50 microns to about 60 microns, about 50 microns to about 70 microns or about 60 microns to about 70 microns. In a preferred embodiment, before densification and before drying, the thickness of the second anode layer can be about 50 microns.

[0100] Before densification and after drying, the thickness of the first anode layer can be about 15 microns to about 50 microns. In some aspects, before densification and after drying, the thickness of the first anode layer can be about 15 microns to about 20 microns, about 20 microns to about 30 microns, about 30 microns to about 40 microns, about 40 microns to about 50 microns, about 15 microns to about 30 microns, about 15 microns to about 40 microns, about 20 microns to about 50 microns, about 30 microns to about 50 microns, or about 40 microns to about 50 microns.

[0101] Typically, the thickness of the first anode layer may be greater than the thickness of the second anode layer. In some embodiments, the thickness of the first anode layer may be about 10% greater than the thickness of the second anode layer, about 20% greater than the thickness of the second anode layer, about 30% greater than the thickness of the second anode layer, about 40% greater than the thickness of the second anode layer, about 50% greater than the thickness of the second anode layer, about 60% greater than the thickness of the second anode layer, or about 70% greater than the thickness of the second anode layer. In an exemplary embodiment, the thickness of the first anode layer is about 40% greater than the thickness of the second anode layer.

[0102] The stacking pressure of about 3000psi or less can be applied to the composition. In certain embodiments, the stacking pressure can be about 3000psi or less, about 2500psi or less, about 2000psi or less, about 1500psi or less, about 1000psi or less, about 750psi or less, about 500psi or less, or about 250psi or less. In an exemplary embodiment, a stacking pressure of about 1500psi or less is applied to the composition. In some further embodiments, the stacking pressure applied to the composition can be about 100 psi to about 250 psi, about 100 psi to about 500 psi, about 100 psi to about 750 psi, about 100 psi to about 1000 psi, about 100 psi to about 1500 psi, about 100 psi to about 2000 psi, about 100 psi to about 2500 psi, about 100 psi to about 3000 psi, about 250 psi to about 3000 psi, about 500 psi to about 3000 psi, about 750 psi to about 3000 psi, about 1000 psi to about 3000 psi, about 1500 psi to about 3000 psi, about 2000 psi to about 3000 psi, about 2500 psi to about 3000 psi, about 2500 psi to about 2500 psi, about 750 psi to about 2000 psi, or about 1000 psi to about 2000 psi.

[0103] After the first cell cycle or a series of conditioning cycles, the composition may form vertical cracks. As used herein, "vertical" cracks refer to cracks that are substantially perpendicular to the boundary (plane) between the anode and the adjacent anode current collector, and have little or no branching in the cracks. In some embodiments, the cracks can be oriented at about 90° ± about 25° relative to the anode current collector; for example, the cracks can be oriented at the following angles: about 65° to about 115°, about 70° to about 110°, about 80° to about 100°, about 85° to about 95°, about 80° to about 90°, about 85° to about 90°, about 90° to about 100°, or about 90° to about 95°. In some additional examples, the cracks can be oriented at an angle of about 65°, 66°, 67°, 68°, 69°, 70°, 71°, 72°, 73°, 74°, 75°, 76°, 77°, 78°, 79°, 80°, 81°, 82°, 83°, 84°, 85°, 86°, 87°, 88°, 89°, 90°, 91°, 92°, 93°, 94°, 95°, 96°, 97°, 98°, 99°, 100°, 101°, 102°, 103°, 104°, 105°, 106°, 107°, 108°, 109°, 110°, 111°, 112°, 113°, 114°, or about 115° relative to the anode current collector. In some further embodiments, the cracks may be orthogonal to the anode current collector.

[0104] Figure 2 An electrochemical cell including an anode bilayer of the present disclosure is shown. The first anode layer 100 includes a plurality of vertical cracks 112. The cracks may form during the first cell cycle of the electrochemical cell or during a series of conditioning cycles.

[0105] The first anode layer may include vertical cracks. In an exemplary embodiment, the first anode layer may have a Figure 2 The second anode layer may comprise vertical cracks.

[0106] In some examples, the second anode layer can have smaller and / or less noticeable cracks than the first anode layer. In some examples, the second anode layer can have no cracks.

[0107] The density of the first anode layer may be about 1.0 g / cm 3 To about 2.0g / cm 3 In some embodiments, the density of the first anode layer may be about 1.0 g / cm 3至约 1.1g / cm 3 , about 1.1g / cm 3 To about 1.2g / cm 3 , about 1.2g / cm3 To about 1.3g / cm 3 , about 1.3g / cm 3 To about 1.4g / cm 3 , about 1.4g / cm 3 To about 1.5g / cm 3 , about 1.5g / cm 3 To about 1.6g / cm 3 , about 1.6g / cm 3 To about 1.7g / cm 3 , about 1.7g / cm 3 To about 1.8g / cm 3 , about 1.8g / cm 3 To about 1.9g / cm 3 , about 1.9g / cm 3 To about 2.0g / cm 3 , about 1.0g / cm 3 To about 1.2g / cm 3 , about 1.0g / cm 3 To about 1.3g / cm 3 , about 1.0g / cm 3 To about 1.4g / cm 3 , about 1.0g / cm 3至约 1.5g / cm 3 , about 1.0g / cm 3 To about 1.6g / cm 3 , about 1.0g / cm 3 To about 1.7g / cm 3 , about 1.0g / cm 3 To about 1.8g / cm 3 , about 1.0g / cm 3 To about 1.9g / cm 3 , about 1.1g / cm 3 To about 2.0g / cm 3 , about 1.2g / cm 3 To about 2.0g / cm 3 , about 1.3g / cm 3 To about 2.0g / cm 3 , about 1.4g / cm 3 To about 2.0g / cm 3 , about 1.5g / cm 3 To about 2.0g / cm 3 , about 1.6g / cm 3 To about 2.0g / cm 3 , about 1.7g / cm 3 To about 2.0g / cm 3, about 1.8g / cm 3 To about 2.0g / cm 3 or about 1.9g / cm 3 To about 2.0g / cm 3 .

[0108] The density of the second anode layer may be equal to or higher than the density of the first anode layer. The density of the second anode layer may be about 1.0 g / cm 3 To about 2.0g / cm 3 In some embodiments, the density of the second anode layer may be about 1.0 g / cm 3至约 1.1g / cm 3 , about 1.1g / cm 3 To about 1.2g / cm 3 , about 1.2g / cm 3 To about 1.3g / cm 3 , about 1.3g / cm 3 To about 1.4g / cm 3 , about 1.4g / cm 3 To about 1.5g / cm 3 , about 1.5g / cm 3 To about 1.6g / cm 3 , about 1.6g / cm 3 To about 1.7g / cm 3 , about 1.7g / cm 3 To about 1.8g / cm 3 , about 1.8g / cm 3 To about 1.9g / cm 3 , about 1.9g / cm 3 To about 2.0g / cm 3 , about 1.0g / cm 3 To about 1.2g / cm 3 , about 1.0g / cm 3 To about 1.3g / cm 3 , about 1.0g / cm 3 To about 1.4g / cm 3 , about 1.0g / cm 3至约 1.5g / cm 3 , about 1.0g / cm 3 To about 1.6g / cm 3 , about 1.0g / cm 3 To about 1.7g / cm 3 , about 1.0g / cm 3 To about 1.8g / cm 3 , about 1.0g / cm 3 To about 1.9g / cm 3, about 1.1g / cm 3 To about 2.0g / cm 3 , about 1.2g / cm 3 To about 2.0g / cm 3 , about 1.3g / cm 3 To about 2.0g / cm 3 , about 1.4g / cm 3 To about 2.0g / cm 3 , about 1.5g / cm 3 To about 2.0g / cm 3 , about 1.6g / cm 3 To about 2.0g / cm 3 , about 1.7g / cm 3 To about 2.0g / cm 3 , about 1.8g / cm 3 To about 2.0g / cm 3 or about 1.9g / cm 3 To about 2.0g / cm 3 .

[0109] The density of any remaining anode layers (e.g., the third anode layer, the fourth anode layer, etc.) may be about 1.0 g / cm 3 To about 2.0g / cm 3 In some embodiments, the density of the anode layer can be about 1.0 g / cm 3至约 1.1g / cm 3 , about 1.1g / cm 3 To about 1.2g / cm 3 , about 1.2g / cm 3 To about 1.3g / cm 3 , about 1.3g / cm 3 To about 1.4g / cm 3 , about 1.4g / cm 3 To about 1.5g / cm 3 , about 1.5g / cm 3 To about 1.6g / cm 3 , about 1.6g / cm 3 To about 1.7g / cm 3 , about 1.7g / cm 3 To about 1.8g / cm 3 , about 1.8g / cm 3 To about 1.9g / cm 3 , about 1.9g / cm 3 To about 2.0g / cm 3 , about 1.0g / cm 3 To about 1.2g / cm 3, about 1.0g / cm 3 To about 1.3g / cm 3 , about 1.0g / cm 3 To about 1.4g / cm 3 , about 1.0g / cm 3至约 1.5g / cm 3 , about 1.0g / cm 3 To about 1.6g / cm 3 , about 1.0g / cm 3 To about 1.7g / cm 3 , about 1.0g / cm 3 To about 1.8g / cm 3 , about 1.0g / cm 3 To about 1.9g / cm 3 , about 1.1g / cm 3 To about 2.0g / cm 3 , about 1.2g / cm 3 To about 2.0g / cm 3 , about 1.3g / cm 3 To about 2.0g / cm 3 , about 1.4g / cm 3 To about 2.0g / cm 3 , about 1.5g / cm 3 To about 2.0g / cm 3 , about 1.6g / cm 3 To about 2.0g / cm 3 , about 1.7g / cm 3 To about 2.0g / cm 3 , about 1.8g / cm 3 To about 2.0g / cm 3 or about 1.9g / cm 3 To about 2.0g / cm 3 .

[0110] The porosity of the first anode layer can be about 25% to about 50%. The method of measuring porosity is well known in the art. In certain embodiments, the porosity of the first anode layer can be about 25% to about 30%, about 25% to about 35%, about 25% to about 40%, about 25% to about 45%, about 30% to about 35%, about 30% to about 40%, about 30% to about 45%, about 30% to about 50%, about 35% to about 40%, about 35% to about 45%, about 35% to about 50%, about 40% to about 45%, about 40% to about 50% or about 45% to about 50%. In an exemplary embodiment, the porosity of the first anode layer is about 40%.

[0111] The porosity of the second anode layer may be from about 10% to about 50%. Typically, the porosity of the second anode layer is lower than the porosity of the first anode layer because the second anode layer expands and contracts less. In some embodiments, the porosity of the second anode layer may be from about 10% to about 15%, from about 10% to about 20%, from about 10% to about 25%, from about 10% to about 30%, from about 10% to about 35%, from about 10% to about 40%, from about 10% to about 45%, from about 15% to about 20%, from about 15% to about 25%, from about 15% to about 30%, from about 15% to about 35%, from about 15% to about 40%, from about 15% to about 45%, from about 15% to about 20%, from about 15% to about 25%, from about 15% to about 30%, from about 15% to about 35%, from about 15% to about 40%, from about 15% to about 45%, from about 15% to about 50%, from about 20% to about 25%, from about 20% to about 30%, From about 20% to about 35%, from about 20% to about 40%, from about 20% to about 45%, from about 20% to about 50%, from about 25% to about 30%, from about 25% to about 35%, from about 25% to about 40%, from about 25% to about 45%, from about 30% to about 35%, from about 30% to about 40%, from about 30% to about 45%, from about 30% to about 50%, from about 35% to about 40%, from about 35% to about 45%, from about 30% to about 50%, from about 35% to about 40%, from about 35% to about 45%, from about 35% to about 50%, from about 40% to about 45%, from about 40% to about 50%, or from about 45% to about 50%.

[0112] The anode layer may be a solid state anode layer.

[0113] exist Figure 1 In the exemplary electrochemical cell shown in , the first anode layer 100 includes about 60 wt% silicon, about 7 wt% styrene-based thermoplastic, about 5 wt% carbon-based conductive additive, and about 28 wt% sulfide solid electrolyte. The second anode layer 102 includes about 30 wt% silicon, about 5 wt% carbon-based conductive additive, about 7 wt% styrene-based thermoplastic, and about 58 wt% sulfide solid electrolyte.

[0114] exist Figure 2 In the exemplary electrochemical cell shown in , the first anode layer 100 includes about 60 wt% silicon, about 7 wt% styrene-based thermoplastic, and about 33 wt% solid electrolyte. The second anode layer 102 includes about 30 wt% silicon, about 5 wt% carbon-based conductive additive, about 45 wt% sulfide solid electrolyte material, and about 20 wt% styrene-based thermoplastic, plasticizer, and tackifier in total.

[0115] Further provided herein is an electrochemical cell comprising the anode bilayer composition of the present disclosure. Figure 1, the electrochemical cell unit includes the anode bilayer of the present disclosure, and the anode bilayer includes a first anode layer 100 and a second anode layer 102; a separator layer 104 and a cathode layer 106. The electrochemical cell unit may further include a cathode current collector 108 and an anode current collector 110.

[0116] The cathode layer 106 may include a cathode active material such as nickel-manganese-cobalt ("NMC"), which may be expressed as Li(Ni a Co b Mn c )O 2 (0 < a < 1, 0 < b < 1, 0 < c < 1, a + b + c = 1) or, for example, NMC 111 (LiNi 0.33 Mn 0.33 Co 0.33 O 2 ), NMC 433 (LiNi 0.4 Mn 0.3 Co 0.3 O 2 ), NMC 532 (LiNi 0.5 Mn 0.3 Co 0. 2O2), NMC 622 (LiNi 0.6 Mn 0.2 Co 0.2 O 2 ), NMC 811 (LiNi 0.8 Mn 0.1 Co 0.1 O 2 ), or a combination thereof. In another embodiment, the cathode active material may include one or more of coated or uncoated metal oxides, such as, but not limited to, V 2 O 5 , V 6 O 13 , MoO 3 , LiCoO 2 , LiNiO 2 , LiMnO 2 , LiMn 2 O 4 , LiNi 1-Y Co Y O 2 , LiCo 1-Y Mn Y O 2 , LiNi 1-Y Mn Y O 2 (0 ≤ Y < 1), Li(Ni a Co b Mn c)O 4 (0 < a < 2, 0 < b < 2, 0 < c < 2, a + b + c = 2), LiMn 2-Z Ni Z O 4 、LiMn 2-Z Co Z O 4 (0 < Z < 2), LiCoPO 4 、LiFePO 4 、CuO、Li(Ni a Co b Al c )O 2 (0 < a < 1, 0 < b < 1, 0 < c < 1, a + b + c = 1) or a combination thereof. In yet another embodiment, the cathode active material may comprise one or more of coated or uncoated metal sulfides, such as but not limited to titanium sulfide (TiS 2 ), molybdenum sulfide (MoS 2 ), iron sulfide (FeS, FeS 2 ), copper sulfide (CuS) and nickel sulfide (Ni 3 S 2 ) or a combination thereof. In still another embodiment, the cathode active material may comprise elemental sulfur (S). In another embodiment, the cathode active material may comprise one or more of fluoride cathode active materials, such as but not limited to lithium fluoride (LiF), sodium fluoride (NaF), calcium fluoride (CaF 2 ), magnesium fluoride (MgF 2 ), nickel(II) fluoride (NiF 2 ), iron(III) fluoride (FeF 3 ), vanadium(III) fluoride (VF 3 ), cobalt(III) fluoride (CoF 3 ), chromium(III) fluoride (CrF 3 ), manganese(III) fluoride (MnF 3 ), aluminum fluoride (AlF 3 ) and zirconium(IV) fluoride (ZrF 4 ) or a combination thereof.

[0117] The cathode layer 106 may further comprise one or more conductive additives. The conductive additives may include metal powders, fibers, filaments or any other known materials for conducting electrons. In some aspects, one or more conductive additives may include one or more conductive carbon materials, such as carbon fibers, graphite, graphene, carbon black, conductive carbon, amorphous carbon, VGCF and carbon nanotubes. In some aspects, the conductive additives may be present in the cathode layer 106 in an amount of about 1% to about 10%.

[0118] The cathode layer 106 may further include one or more solid electrolytes. The one or more solid electrolytes may include oxides, sulfur oxides, sulfides, halides, nitrides, or any other solid electrolytes known in the art. In some preferred embodiments, the one or more solid electrolytes may include sulfide solid electrolytes. In some embodiments, the solid electrolyte includes one or more material combinations, such as Li 2 SP 2 S 5 , Li 2 SP 2 S 5 -LiI, Li 2 SP 2 S 5 -GeS 2 , Li 2 SP 2 S 5 -Li 2 O. Li 2 SP 2 S 5 -Li 2 O-LiI、Li 2 SP 2 S 5 -LiI-LiBr, Li 2 S-SiS 2 , Li 2 S-SiS 2 -LiI, Li 2 S-SiS 2 -LiBr, Li 2 SS-SiS 2 -LiCl, Li 2 SS-SiS 2 -B 2 S 3 -LiI, Li 2 SS-SiS 2 -P 2 S 5 -LiI, Li 2 SB 2 S 3 , Li 2 SP 2 S 5 -Z m S n (where m and n are positive numbers, and Z is Ge, Zn or Ga), Li 2 S-GeS 2 , Li 2 SS-SiS 2 -Li 3 PO4 and Li 2 S - S - SiS 2 -Li x MO y (where x and y are positive numbers, and M is P, Si, Ge, B, Al, Ga, or In). In another embodiment, the solid electrolyte can be one or more of the following: Li 3 PS 4 、Li 4 P 2 S 6 、Li 7 P 3 S 11 、Li 10 GeP 2 S 12 、Li 10 SnP 2 S 12 。In additional embodiments, the solid electrolyte can be one or more of the following: Li 6 PS 5 Cl、Li 6 PS 5 Br、Li 6 PS 5 I or represented by the formula Li 7-y PS 6-y X y where "X" represents at least one halogen and / or at least one pseudohalogen and where 0 < y ≤ 2.0, and where the at least one halogen can be one or more of the following: F, Cl, Br, I, and the at least one pseudohalogen can be one or more of the following: N, NH, NH 2 、NO、NO 2 、BF 4 、BH 4 、AlH 4 、CN and SCN. In yet another embodiment, the solid electrolyte is represented by the formula Li 8-y-z P 2 S 9-y-z X y W z (where "X" and "W" represent at least one halogen element and / or pseudohalogen and where 0 ≤ y ≤ 1 and 0 ≤ z ≤ 1), and where the halogen can be one or more of the following: F, Cl, Br, I, and the pseudohalogen can be one or N, NH, NH 2 、NO、NO 2 、BF 4 、BH 4 、AlH 4, CN and SCN. In some aspects, the solid electrolyte may be present in the cathode layer 106 in an amount of about 5% to about 20%. The halide solid electrolyte may have a Li-MX structure, M is a metal element, and X is a halogen. These can be represented by the general formula Li α M 4+ β N 3+ (1-β) X Ω Y (6-Ω) To represent, where: 0≤β≤1; 0≤Ω≤6; α=6-[(β*4)+(1-β)*3]; X and Y are halogens, such as F, Cl, Br, I; M is an element with an oxidation state of 4+, such as Ti, Zr, Hf and Rf; N is an element with an oxidation state of 3+, such as Ga, In and Tl, Sc, Y, Fe, Ru, Os, Er. Examples of halide electrolytes include Li 2 ZrCl 6 , Li 3 InCl 6 , Li 2.25 Hf 0.75 Fe 0.25 Cl 4 Br 2 .

[0119] In other embodiments, the cathode layer may include a semi-solid electrolyte or a liquid electrolyte.

[0120] The cathode layer 106 may further include one or more of the binders. In some embodiments, the binder may include a fluororesin containing vinylidene fluoride (VdF), hexafluoropropylene (HFP), tetrafluoroethylene (TFE) and its derivatives as structural units. Specific examples thereof include homopolymers such as polyvinylidene fluoride (PVdF), polyhexafluoropropylene (PHFP) and polytetrafluoroethylene (PTFE); and binary copolymers such as copolymers of VdF and HFP, such as poly(vinylidene fluoride-hexafluoropropylene) copolymer (PVdF-HFP) and the like. In another embodiment, the binder may be one or more of thermoplastic elastomers, such as but not limited to styrene-butadiene rubber (SBR), styrene-butadiene-styrene copolymer (SBS), styrene-isoprene block copolymer (SIS), styrene-ethylene-butylene-styrene (SEBS), polyacrylonitrile (PAN), nitrile-butene rubber (NBR), polybutadiene, polyisoprene, poly(methacrylate) nitrile-butadiene rubber (PMMA-NBR), and the like. In other embodiments, the binder can be one or more of acrylic resins, such as but not limited to poly(methyl)acrylate, poly(ethyl)acrylate, poly(isopropyl)acrylate, poly(isobutyl)acrylate, poly(butyl)acrylate, etc. In another embodiment, the binder can be one or more of condensation polymers, such as but not limited to polyurea, polyamide paper, polyimide, polyester, etc. In other embodiments, the binder can include cellulose binders such as carboxymethyl cellulose (CMC). In another embodiment, the binder can be one or more of nitrile rubbers, such as but not limited to acrylonitrile-butadiene rubber (ABR), polystyrene nitrile-butadiene rubber (PS-NBR) and mixtures thereof. In other embodiments, the binder can be one or more of styrene-based thermoplastics, such as but not limited to styrene-butadiene rubber (SBR), styrene-butadiene-styrene block copolymer (SBS), styrene-isoprene block copolymer (SIS) or styrene-ethylene-butylene-styrene block copolymer (SEBS). In other embodiments, the binder may include one or more of: styrene-butadiene rubber (SBR), polyvinylidene fluoride (PVdF), carboxymethyl cellulose (CMC), or a combination thereof or a derivative thereof.

[0121] In some embodiments, the binder may include one or more rheology-modifying components. In some preferred embodiments, when the binder includes one or more rheology-modifying components, the binder further includes one or more additional binders or polymers that are not rheology-modifying components. In some aspects, the binder may be present in the cathode layer 106 in an amount of about 0% to about 5%.

[0122] The separator layer 104 (also referred to herein as an "electrolyte layer") may include one or more solid electrolytes. The one or more solid electrolytes may include oxides, sulfur oxides, sulfides, halides, nitrides, or any other solid electrolytes known in the art. In some preferred embodiments, the one or more solid electrolytes may include sulfide solid electrolytes. In some aspects, the one or more sulfide solid electrolytes may include one or more material combinations, such as Li 2 S—P 2 S 5 , Li 2 S—P 2 S 5 —LiI, Li 2 S—P 2 S 5 —GeS 2 , Li 2 S—P 2 S 5 —Li 2 O. Li 2 S—P 2 S 5 —Li 2 O—LiI, Li 2 SP 2 S 5 —LiI—LiBr, Li 2 S—SiS 2 , Li 2 S—SiS 2 —LiI, Li 2 S—SiS 2 —LiBr, Li 2 S—S—SiS 2 —LiCl, Li 2 S—S—SiS 2 —B 2 S 3 —LiI, Li 2 S—S—SiS 2 —P 2 S 5 —LiI, Li 2 S—B 2 S 3 , Li 2 S—P 2 S 5 —Z m S n (where m and n are positive numbers, and Z is Ge, Zn or Ga), Li 2 S-GeS 2 , Li 2 SS-SiS 2-Li 3 PO 4 and Li 2 S - S - SiS 2 -Li x MO y (where x and y are positive numbers, and M is P, Si, Ge, B, Al, Ga, or In). In some embodiments, one or more of the solid electrolyte materials can be Li 3 PS 4 , Li 4 P 2 S 6 , Li 7 P 3 S 11 , Li 10 GeP 2 S 12 , Li 10 SnP 2 S 12 . In another embodiment, one or more of the solid electrolyte materials can be Li 6 PS 5 Cl, Li 6 PS 5 Br, Li 6 PS 5 I or represented by the formula Li 7-y PS 6-y X y , where "X" represents at least one halogen and / or at least one pseudohalogen, where 0 < y ≤ 2.0, and where the halogen can be one or more of the following: F, Cl, Br, I, and the pseudohalogen can be one or more of the following: N, NH, NH 2 , NO, NO 2 , BF 4 , BH 4 , AlH 4 , CN, and SCN. In yet another embodiment, one or more of the solid electrolyte materials can be represented by the formula Li 8-y-z P 2 S 9-y-z X y W z (where "X" and "W" represent at least one halogen and / or at least one pseudohalogen, and where 0 ≤ y ≤ 1 and 0 ≤ z ≤ 1), and where the halogen can be one or more of the following: F, Cl, Br, I, and the pseudohalogen can be one or more of the following: N, NH, NH 2 , NO, NO 2 , BF 4 , BH 4 , AlH4 , CN and SCN. The halide solid electrolyte can have a Li-MX structure, M is a metal element, and X is a halogen. These can be represented by the general formula Li α M 4+ β N 3+ (1-β) X Ω Y (6-Ω) To represent, where: 0≤β≤1; 0≤Ω≤6; α=6-[(β*4)+(1-β)*3]; X and Y are halogens, such as F, Cl, Br, I; M is an element with an oxidation state of 4+, such as Ti, Zr, Hf and Rf; N is an element with an oxidation state of 3+, such as Ga, In and Tl, Sc, Y, Fe, Ru, Os, Er. Examples of halide electrolytes include Li 2 ZrCl 6 , Li 3 InCl 6 , Li 2.25 Hf 0.75 Fe 0.25 Cl 4 Br 2 .

[0123] In other embodiments, the separator layer may include a semi-solid electrolyte or a liquid electrolyte.

[0124] The diaphragm layer 104 may further include one or more of the binders. In some embodiments, the binder may include a fluororesin containing vinylidene fluoride (VdF), hexafluoropropylene (HFP), tetrafluoroethylene (TFE) and its derivatives as structural units. Specific examples thereof may include homopolymers such as polyvinylidene fluoride (PVdF), polyhexafluoropropylene (PHFP) and polytetrafluoroethylene (PTFE); and binary copolymers such as copolymers of VdF and HFP, such as poly(vinylidene fluoride-hexafluoropropylene) copolymer (PVdF-HFP) and the like. In another embodiment, the binder may be one or more of thermoplastic elastomers, such as but not limited to styrene-butadiene rubber (SBR), styrene-butadiene-styrene copolymer (SBS), styrene-isoprene block copolymer (SIS), styrene-ethylene-butylene-styrene (SEBS), polyacrylonitrile (PAN), nitrile-butene rubber (NBR), polybutadiene, polyisoprene, poly(methacrylate) nitrile-butadiene rubber (PMMA-NBR), and the like. In other embodiments, the binder may be one or more of acrylic resins, such as but not limited to poly(methyl)acrylate, poly(ethyl)acrylate, poly(isopropyl)acrylate, poly(isobutyl)acrylate, poly(butyl)acrylate, etc. In yet another embodiment, the binder may be one or more of condensation polymers, such as but not limited to polyurea, polyamide paper, polyimide, polyester, etc. In yet another embodiment, the binder may be one or more of nitrile rubbers, such as but not limited to acrylonitrile-butadiene rubber (ABR), polystyrene nitrile-butadiene rubber (PS-NBR) and mixtures thereof. In some embodiments, the binder may include one or more rheology-modifying components. In some preferred embodiments, when the binder includes one or more rheology-modifying components, the binder further includes one or more other binders or polymers that are not rheology-modifying components. In some aspects, the binder may be present in the diaphragm layer 104 in an amount of about 0 wt % to about 20 wt %.

[0125] In some embodiments, the thickness of the membrane layer 104 can be about 10-40 μm. In some aspects, the thickness of the membrane layer 104 can be about 10 μm to about 20 μm, about 10 μm to about 30 μm, about 20 μm to about 30 μm, about 20 μm to about 40 μm, or about 30 μm to about 40 μm. In some additional aspects, the thickness of the diaphragm layer 104 can be about 10μm, 11μm, 12μm, 13μm, 14μm, 15μm, 16μm, 17μm, 18μm, 19μm, 20μm, 21μm, 22μm, 23μm, 24μm, 25μm, 26μm, 27μm, 28μm, 29μm, 30μm, 31μm, 32μm, 33μm, 34μm, 35μm, 36μm, 37μm, 38μm, 39μm or about 40μm.

[0126] The cathode current collector 108 is disposed adjacent to the cathode layer 106, and the anode current collector 110 is disposed adjacent to the first anode layer 100. The cathode current collector 108 and the anode current collector 110 may include one or more of the following: copper, nickel, titanium, stainless steel, magnesium, iron, zinc, indium, germanium, silver, platinum, or gold. In some embodiments, the thickness of the cathode current collector 108 or the anode current collector 110 may be about 5 μm to about 10 μm. In a preferred embodiment, the cathode current collector 108 includes aluminum, nickel, and / or steel. In another preferred embodiment, the anode current collector 110 includes copper.

[0127] The electrochemical cell can be cycled while applying a stacking pressure of up to 3000 psi. In some embodiments, the stacking pressure can be about 3000 psi or less, about 2500 psi or less, about 2000 psi or less, about 1500 psi or less, about 1000 psi or less, about 750 psi or less, about 500 psi or less, or about 250 psi or less. In an exemplary embodiment, a stacking pressure of about 1500 psi or less is applied to the composition. In some further embodiments, the stacking pressure applied to the composition can be about 100 psi to about 250 psi, about 100 psi to about 500 psi, about 100 psi to about 750 psi, about 100 psi to about 1000 psi, about 100 psi to about 1500 psi, about 100 psi to about 2000 psi, about 100 psi to about 2500 psi, about 100 psi to about 3000 psi, about 250 psi to about 3000 psi, about 500 psi to about 3000 psi, about 750 psi to about 3000 psi, about 1000 psi to about 3000 psi, about 1500 psi to about 3000 psi, about 2000 psi to about 3000 psi, about 2500 psi to about 3000 psi, about 2500 psi to about 2500 psi, about 750 psi to about 2000 psi, or about 1000 psi to about 2000 psi.

[0128] The electrochemical cell can be cycled at a temperature of about 10° C. to about 50° C. In some embodiments, the electrochemical cell can be cycled at a temperature of about 10° C. to about 20° C., about 10° C. to about 30° C., about 10° C. to about 40° C., about 10° C. to about 50° C., about 20° C. to about 30° C., about 20° C. to about 40° C., about 20° C. to about 50° C., about 30° C. to about 40° C., about 30° C. to about 50° C., or about 40° C. to about 50° C. For example, the electrochemical cell can be cycled at a temperature of about 10° C., 15° C., 20° C., 25° C., 30° C., 35° C., 40° C., 45° C., or about 50° C.

[0129] Generally, when a higher stacking pressure is applied during the first cell cycle, the electrochemical cell can have a greater capacity retention rate than an electrochemical cell to which a smaller stacking pressure is applied during the first cell cycle. Without wishing to be bound by theory, the increased stacking pressure improves contact between particles and layers, reduces resistance, and promotes the formation of vertical cracks. However, if the stacking pressure is too high, the cell may short circuit.

[0130] In general, the capacity retention of the electrochemical cell of the present disclosure may be higher than that of an electrochemical cell containing a single-layer anode. The capacity retention rate is a measure of the capacity of an electrochemical cell after cycling as a percentage of the initial capacity of the electrochemical cell. The capacity retention rate of the electrochemical cell of the present disclosure may be up to about 99.9%. For example, the capacity retention rate of the electrochemical cell may be about 99.9%, about 99.5%, about 99%, about 95%, about 90%, about 85%, about 80%, about 99.9% to about 99.5%, about 99.9% to about 95%, about 99.9% to about 90%, about 99.9% to about 85%, about 99.9% to about 80%. In addition, the capacity retention rate of the electrochemical cell may be at least about 80%, at least about 85%, at least about 90%, at least about 95%, at least about 99%, at least about 99.5%, or at least about 99.9%. The capacity retention may be at least 80% after about 100 cycles, 200 cycles, 300 cycles, 400 cycles, 500 cycles, 600 cycles, 700 cycles, 800 cycles, or after greater than 800 cycles.

[0131] Additionally, the discharge capacity of the electrochemical cell of the present disclosure can be stable over more cycles compared to an electrochemical cell comprising a single-layer anode. As used herein, a "stable" electrochemical cell is a cell having a discharge capacity of 80% or more of the discharge capacity of the electrochemical cell after the first complete cycle. By way of non-limiting example, an electrochemical cell having a discharge capacity of 100 mAh after the first cycle is considered stable if the discharge capacity of the cell is 80 mAh or more after 100 cycles. For example, the electrochemical cell can have a stable discharge capacity for at least 100 cycles, at least 150 cycles, at least 200 cycles, at least 250 cycles, at least 300 cycles, at least 400 cycles, at least 500 cycles, at least 600 cycles, at least 700 cycles, or at least 800 cycles.

[0132] The electrochemical cells of the present disclosure may have lower internal resistance compared to electrochemical cells containing a single layer anode.

[0133] When an electrochemical cell containing a single layer anode is cycled, the anode layer has a tendency to separate from the separator layer due to expansion and contraction of the anode. In the electrochemical cell of the present disclosure, the anode bilayer does not separate from the separator layer when the cell is cycled at a stack pressure of less than 1500 psi.

[0134] Additionally, due to the reduced expansion and contraction of the double-layer anode, the double-layer anode has better surface area contact with the separator layer than an electrochemical cell with a single-layer anode. Therefore, there may be less void space between the double-layer anode and the separator layer than an electrochemical cell with a single-layer anode. The surface area in contact with the separator layer can be determined by SEM imaging.

[0135] Also provided herein is a method for preparing a double-layer anode for a solid electrochemical cell. The method may include: a) forming a first anode slurry by mixing an anode active material, optionally at least one solid electrolyte material, at least one binder material, and a solvent; b) forming a second anode layer slurry by: mixing an anode active material, at least one solid electrolyte material, at least one binder material, optionally at least one viscosity enhancer, optionally at least one plasticizer, and a solvent; c) casting the first anode layer slurry onto a substrate; d) casting the second anode layer slurry onto the first anode layer slurry; and e) drying the first anode layer slurry and the second anode layer slurry to form an anode double layer. In some embodiments, there may be an intermediate drying step before step d) comprising drying the first layer slurry. In steps a) and b), the components for forming the slurry may be mixed in any order or sequence. As a non-limiting example, the anode active material, at least one solid electrolyte material, and at least one binder material may be mixed before adding a solvent to form a slurry. Alternatively, as another non-limiting example, each of the anode active material, the at least one solid electrolyte material, and the at least one binder material may be added sequentially to the solvent while being mixed.

[0136] In an alternative embodiment, the method may include: a) forming a first anode slurry by mixing an anode active material, optionally at least one solid electrolyte material, at least one binder material, and a solvent; b) forming a second anode layer slurry by mixing an anode active material, at least one solid electrolyte material, at least one binder material, optionally at least one viscosity enhancer, optionally at least one plasticizer, and a solvent; c) casting the first anode layer slurry onto a substrate and drying the first anode layer slurry; d) casting the second anode layer slurry onto the first anode layer slurry and drying the second anode layer slurry.

[0137] In some embodiments, the solvent may be selected from, but not limited to, one of the following: aprotic hydrocarbons, esters, ethers, or nitrile. On the other hand, aprotic hydrocarbons may be selected from, but not limited to, one of the following: xylene, toluene, benzene, methylbenzene, hexane, heptane, octane, alkane, isoparaffin, or a combination thereof. On the other hand, esters may be selected from, but not limited to, one of the following: butyl butyrate, isobutyl isobutyrate, methyl propionate, ethyl propionate, propyl propionate, butyl propionate, methyl acetate, ethyl acetate, propyl acetate, butyl acetate, or a combination thereof. On the other hand, ethers may be selected from, but not limited to, one of the following: diethyl ether, dibutyl ether, benzyl ether, or a combination thereof. On the other hand, nitrile may be selected from, but not limited to, one of the following: acetonitrile, propionitrile, butyronitrile, pyrrolidine, or a combination thereof. The solvent used to form the first layer of slurry may be the same or different from the solvent used to form the second layer of slurry.

[0138] After drying the anode bilayer on the substrate, the anode bilayer can be densified to increase the density of the anode bilayer. Densification methods are well known to those skilled in the art. In a preferred embodiment, densification is accomplished by calendering or by pressing (e.g., with a linear press). In some embodiments, the temperature during densification can be from about 80°C to about 140°C. It should be understood that the density of the anode layer will depend on the formulation of the anode layer and the densification conditions. Without wishing to be bound by theory, increasing the density of the anode bilayer reduces the porosity of the anode bilayer, thereby improving contact between particles and reducing the resistance of the anode bilayer.

[0139] Exemplary Embodiments

[0140] Embodiment 1: An anode composition comprising:

[0141] a first anode layer, the first anode layer being in operative contact with a second anode layer, the first anode layer and the second anode layer each comprising:

[0142] an anode active material; and

[0143] Binder,

[0144] wherein the second anode layer further comprises a solid electrolyte material, and

[0145] Wherein the first anode layer optionally comprises a solid electrolyte material.

[0146] Embodiment 2: The anode composition of embodiment 1, wherein the anode active material is present in the first layer in an amount greater than or equal to about 50% by weight of the first layer.

[0147] Embodiment 3: The anode composition of embodiment 1 or 2, wherein the anode active material is present in the second anode layer in an amount from about 20 wt % to about 70 wt % of the second anode layer.

[0148] Embodiment 4: The anode composition according to any one of Embodiments 1 to 3, wherein the anode active material of the first anode layer comprises an inorganic material.

[0149] Embodiment 5: The anode composition according to embodiment 4, wherein the inorganic material is selected from the group consisting of silicon, silicon alloys, tin, tin alloys, germanium, germanium alloys, and combinations thereof.

[0150] Embodiment 6: The anode composition according to embodiment 5, wherein the inorganic material is silicon, a silicon alloy or a combination thereof.

[0151] Embodiment 7: The anode composition of any one of Embodiments 1 to 6, wherein the first anode layer comprises about 5% or less of a solid electrolyte material.

[0152] Embodiment 8: The anode composition of any one of Embodiments 1 to 7, wherein the first anode layer comprises about 1% or less of a solid electrolyte material.

[0153] Embodiment 9: The anode composition of any one of Embodiments 1 to 8, wherein the first anode layer does not include a solid electrolyte material.

[0154] Embodiment 10: The anode composition of any one of Embodiments 1 to 9, wherein the solid electrolyte material comprises a sulfide-based solid electrolyte material.

[0155] Embodiment 11: The anode composition of any one of Embodiments 1 to 10, wherein the binder of the first anode layer is different from the binder in the second anode layer.

[0156] Embodiment 12: The anode composition according to any one of embodiments 1 to 11, wherein the binder comprises one or more of the following: styrene-butadiene rubber (SBR), polyvinylidene fluoride (PVdF), carboxymethyl cellulose (CMC) or a combination thereof or a derivative thereof.

[0157] Embodiment 13: The anode composition of any one of Embodiments 1 to 12, further comprising a current collector in operable contact with the first anode layer.

[0158] Embodiment 14: The anode composition of any one of Embodiments 1 to 13, wherein the first anode layer or the second anode layer further comprises a carbon-based conductive additive.

[0159] Embodiment 15: The anode composition of claim 14, wherein the carbon-based conductive additive is selected from the group consisting of graphite, graphene, carbon black, carbon nanotubes, carbon nanowires, vapor-grown carbon fibers, activated carbon, and combinations thereof.

[0160] Embodiment 16: The anode composition of claim 1, wherein the second anode layer further comprises an adhesion promoter.

[0161] Embodiment 17: The anode composition of claim 16, wherein the viscosity promoter comprises a hydrocarbon resin.

[0162] Embodiment 18: The anode composition of claim 1, wherein the second anode layer further comprises a plasticizer.

[0163] Embodiment 19: The anode composition of claim 18, wherein the plasticizer comprises dioctyl phthalate, dibutyl sebacate, mineral oil, or a combination thereof.

[0164] Embodiment 20: The anode composition according to claim 1, further comprising a third anode layer, wherein the third anode layer comprises

[0165] Anode active material;

[0166] Binder;

[0167] Conductive additives; and

[0168] solid electrolyte material; and

[0169] The weight percentage amounts of anode active material, binder, conductive additive and / or solid electrolyte material in the third anode layer are different from those in the first anode layer and the second anode layer.

[0170] Embodiment 21: A method for preparing the anode composition according to claim 1, the method comprising:

[0171] a) forming a first anode layer slurry by: mixing an anode active material, optionally at least one solid electrolyte material, at least one binder material, and a solvent;

[0172] b) forming a second anode layer slurry by: mixing an anode active material, at least one solid electrolyte material, at least one binder material, and a solvent;

[0173] c) casting the first anode layer slurry onto a substrate;

[0174] d) casting the second anode layer slurry onto the first anode layer slurry; and

[0175] e) drying the first anode layer slurry and the second anode layer slurry to form the anode composition.

[0176] Embodiment 22: The method of claim 21, wherein the mixing in step a) comprises mixing an anode active material, at least one solid electrolyte material, and at least one binder material, wherein the solid electrolyte material is substantially excluded from the combining.

[0177] Embodiment 23: The method according to claim 21 or 22, wherein the mixing in step a) does not include at least one solid electrolyte material.

[0178] Embodiment 24: A method for preparing the anode composition according to claim 1, the method comprising:

[0179] a) forming a first anode layer slurry by: mixing an anode active material, optionally at least one solid electrolyte material, at least one binder material, and a solvent;

[0180] b) forming a second anode layer slurry by mixing an anode active material, at least one solid electrolyte material, at least one binder material, optionally at least one plasticizer, optionally at least one viscosity enhancer, and a solvent;

[0181] c) casting the first anode layer slurry onto a substrate, and drying the first anode layer slurry; and

[0182] d) casting the second anode layer slurry onto the first anode layer slurry, and drying the second anode layer slurry.

[0183] Embodiment 25: A composition comprising a solid double-layer anode, the double-layer anode comprising:

[0184] A first anode layer, the first anode layer comprising:

[0185] a first anode active material, wherein the first anode active material is present in the first anode layer in an amount greater than or equal to about 50% by weight of the first anode layer;

[0186] a first binder; and

[0187] a first conductive additive;

[0188] A second anode layer, the second anode layer comprising:

[0189] a second anode active material, wherein the second anode active material is present in the second anode layer in an amount from about 20% to about 70% by weight of the second anode layer;

[0190] a second binder;

[0191] a second conductive additive; and

[0192] Solid electrolyte materials.

[0193] Embodiment 26: The composition of claim 25, wherein the first anode layer comprises substantially no solid electrolyte material.

[0194] Embodiment 27: The composition of claim 25, wherein the first anode layer is free of solid electrolyte material.

[0195] Embodiment 28: The composition of claim 25, wherein the anode active material is present in the first layer in an amount greater than or equal to about 50% by weight of the first layer.

[0196] Embodiment 29: The composition of claim 25, wherein the anode active material is present in the second anode layer in an amount from about 20 wt % to about 50 wt % of the second anode layer.

[0197] Embodiment 30: The composition of claim 25, wherein the anode active material of the first anode layer comprises an inorganic material.

[0198] Embodiment 31: The composition of claim 30, wherein the inorganic material is selected from the group consisting of silicon, silicon alloys, tin, tin alloys, germanium, germanium alloys, and combinations thereof.

[0199] Embodiment 32: The composition of claim 31, wherein the inorganic material is silicon, a silicon alloy, or a combination thereof.

[0200] Embodiment 33: The composition of claim 25, wherein the first anode layer comprises about 5% or less of a solid electrolyte material.

[0201] Embodiment 34: The composition of claim 25, wherein the first anode layer comprises about 1% or less of a solid electrolyte material.

[0202] Embodiment 35: The composition of claim 25, wherein the solid electrolyte material comprises a sulfide-based solid electrolyte material.

[0203] Embodiment 36: The composition of claim 25, wherein the binder of the first anode layer is different from the binder in the second anode layer.

[0204] Embodiment 37: The composition of claim 25, wherein the binder comprises one or more of: styrene-butadiene rubber (SBR), polyvinylidene fluoride (PVdF), carboxymethyl cellulose (CMC), or a combination thereof or a derivative thereof.

[0205] Embodiment 38: The composition of claim 25, further comprising a current collector in operable contact with the first anode layer.

[0206] Embodiment 39: The composition of claim 25, wherein the first anode layer or the second anode layer further comprises a carbon-based conductive additive.

[0207] Embodiment 40: The composition of claim 39, wherein the carbon-based conductive additive is selected from the group consisting of graphite, graphene, carbon black, carbon nanotubes, carbon nanowires, vapor grown carbon fibers, activated carbon, and combinations thereof.

[0208] Embodiment 41: The composition of claim 25, wherein the second anode layer further comprises an adhesion promoter.

[0209] Embodiment 42: The composition of claim 41 wherein the tackifier comprises a hydrocarbon resin.

[0210] Embodiment 43: The composition of claim 25, wherein the second anode layer further comprises a plasticizer.

[0211] Embodiment 44: The composition of claim 43, wherein the plasticizer comprises dioctyl phthalate, dibutyl sebacate, mineral oil, or a combination thereof.

[0212] Embodiment 45: A composition comprising a solid double-layer anode, the double-layer anode comprising:

[0213] A first anode layer, the first anode layer comprising:

[0214] a first anode active material, the first anode active material being in an amount of about 60 weight percent or more of the first anode layer;

[0215] a first solid electrolyte material, the first solid electrolyte material being in an amount of about 20 wt % to about 30 wt % of the first anode layer; and

[0216] a first binder, the first binder being present in an amount of about 0 wt % to about 20 wt % of the first anode layer; and

[0217] A second anode layer, the second anode layer comprising:

[0218] a second anode active material, the second anode active material being in an amount from about 20 wt % to about 70 wt % of the second anode layer;

[0219] a second solid electrolyte material, the second solid electrolyte material being in an amount of about 45 weight percent or less of the second anode layer; and

[0220] A second binder, the second binder being in an amount of about 10 weight percent or less of the second anode layer.

[0221] Embodiment 46: An electrochemical cell comprising:

[0222] A double-layer anode, the double-layer anode comprising:

[0223] a first anode layer, the first anode layer being in operative contact with a second anode layer, the first anode layer and the second anode layer each comprising:

[0224] an anode active material; and

[0225] Binder,

[0226] wherein the second anode layer further comprises a solid electrolyte material, and

[0227] wherein the first anode layer optionally comprises a solid electrolyte material;

[0228] The diaphragm layer, and

[0229] Cathode layer.

[0230] Embodiment 47: The electrochemical cell of claim 46, further comprising a first current collector in operable contact with the first anode layer of the bilayer anode.

[0231] Embodiment 48: The composition of claim 46, wherein the first anode layer comprises substantially no solid electrolyte material.

[0232] Embodiment 49: The composition of claim 46, wherein the first anode layer is free of solid electrolyte material.

[0233] Those skilled in the art will appreciate that the above-described method for forming an anode bilayer may be performed to form an anode composition having three or more layers by repeating the steps described above.

[0234] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those generally understood by those of ordinary skill in the art to which the present disclosure belongs. Although any methods and materials similar to or equivalent to the methods and materials described herein may be used in the practice or testing of the subject matter of the present disclosure, preferred methods and materials are described. For purposes of the present disclosure, the following terms are defined below.

[0235] Concentrations, amounts, and other numerical data may be expressed or presented in this article in a range format. It should be understood that such range formats are used only for convenience and brevity, and should be flexibly interpreted as including not only the values ​​explicitly stated as the limits of the range, but also all individual values ​​or subranges within the range, as if each value and subrange were explicitly stated. As an illustration, a numerical range of "about 2 to about 50" should be interpreted as including not only the values ​​of 2 to 50 explicitly stated, but also all individual values ​​and subranges within the indicated range. Thus, within this numerical range are included individual values ​​such as 2, 2.4, 3, 3.7, 4, 5.5, 10, 10.1, 14, 15, 15.98, 20, 20.13, 23, 25.06, 30, 35.1, 38.0, 40, 44, 44.6, 45, 48, and subranges such as 1-3, 2-4, 5-10, 5-20, 5-25, 5-30, 5-35, 5-40, 5-50, 2-10, 2-20, 2-30, 2-40, 2-50, and the like. This same principle applies to ranges that list only one value as a minimum or maximum. Furthermore, such an interpretation should apply no matter how large the range or characteristic being described is.

[0236] The term "about" will be understood by those of ordinary skill in the art and will vary to some extent depending on the context in which it is used. As used herein, when referring to measurable values ​​such as amounts, time durations, etc., the term "about" is meant to encompass variations of ±10% (including ±5%, ±1%, and ±0.1%) from the specified value, as such variations are suitable for performing the disclosed methods.

[0237] In the present disclosure, "comprise / comprising", "containing", and "having", etc. may have the meanings assigned to them by U.S. patent law and may mean "include / including", etc., and are generally interpreted as open-ended terms. The term "consisting of or consists of" is a closed term and includes only the components, structures, steps, etc. specifically listed in conjunction with such terms and the components, structures, steps, etc. that comply with U.S. patent law. "Consisting essentially of or consists essentially of" has the meaning generally assigned to it by U.S. patent law. In particular, such terms are generally closed terms, except that additional items, materials, components, components, steps, or elements are allowed to be included, which do not materially affect the basic and novel characteristics or functions of the items associated therewith. For example, if a trace element is present in a composition, but does not affect the properties or characteristics of the composition, it is allowed if it is present in the expression "essentially consisting of", even if it is not explicitly listed in the list of items following such terms. In this specification, when open-ended terms such as "comprising" or "including" are used, it should be understood that direct support should also be provided for "consisting essentially of" language and "consisting of" statements, as if explicitly stated, and vice versa.

[0238] Examples

[0239] Examples are set forth below for the purpose of illustrating and describing certain specific embodiments of the present disclosure. However, the scope of the claims is not limited in any way by the examples set forth herein. Various changes and modifications to the disclosed embodiments will be apparent to those skilled in the art, and such changes and modifications may be made without departing from the spirit of the present disclosure and the scope of the appended claims, including but not limited to changes and modifications involving chemical structures, substituents, derivatives, formulations, or methods of the present disclosure. The definitions of the variables in the structures in the schemes herein are consistent with the definitions of the corresponding positions in the formulas given herein.

[0240] Example 1: Double-layer anode cycling data - no adhesion promoter or plasticizer

[0241] Four electrochemical cells were manufactured. Two electrochemical cells included a single anode layer and two electrochemical cells contained an anode bilayer of the present disclosure. The separator layer and cathode layer of each of the four cells were identical. Table 1 below provides the composition of the anode layer of the four electrochemical cells. The styrene-based thermoplastic and sulfide-based solid electrolyte (SSE) were the same for all electrochemical cells. All percentages are weight percentages.

[0242] Table 1

[0243]

[0244] The cells were cycled at 29°C at a stack pressure of 300 psi. The cycling data are given in Figures 3A-3D The data of battery cell number 1 are shown as hollow squares (□), the data of battery cell number 2 are shown as (◇), the data of battery cell number 3 are shown as hollow circles (○), and the data of battery cell number 4 are shown as solid circles (●). The data show that the battery cell with the anode double layer is stable and lasts for more than 100 cycles.

[0245] Example 2: Bi-layer Anode Cycling Data - Cells Including Adhesive and Plasticizer

[0246] Electrochemical cells comprising double-layer anodes and single-layer anodes were manufactured. Three electrochemical cells comprising double-layer anodes were manufactured, and two electrochemical cells comprising single-layer anodes were manufactured. The double-layer anodes included a plasticizer and a tackifier in the second anode layer, and the single-layer anodes also included a plasticizer and a tackifier. The plasticizer included mineral oil. The tackifier included a hydrocarbon resin. The styrene-based thermoplastic and the sulfide-based solid electrolyte (SSE) were the same for all electrochemical cells. The composition of the anode layer of each cell is provided in Table 2 below. All percentages are weight percentages.

[0247] Table 2

[0248]

[0249] The cycling data of these battery cells is Figures 4A-4C The double-layer anode is shown as a solid circle (●), and the single-layer anode is shown as a hollow circle (○). The battery cell with a double-layer anode having a high concentration of styrene-based thermoplastics, plasticizers, and thickeners at the interface of the separator has a better capacity retention rate than the battery cell with a single layer of styrene-based thermoplastics, plasticizers, and thickeners. The data shows that the presence of a thickener and / or plasticizer alone does not improve the performance of the anode. On the contrary, the double-layer structure of the anode provides improved performance of the electrochemical battery cell.

[0250] Example 3: Double-layer anode cycle data - Effect of adhesion promoter and plasticizer in double-layer anode

[0251] Electrochemical cells containing a double layer anode were fabricated. Three cells included a tackifier and a plasticizer in the second anode layer, and three cells did not include a tackifier or a plasticizer. The composition of the anode layer of each cell is provided in Table 3 below. For the first three cycles, the cell was charged for more than three hours and discharged for more than three hours, and then for the remaining cycles, charged for more than five hours and discharged for more than five hours. All percentages are expressed by weight percentage.

[0252] Table 3

[0253]

[0254] The cycling data of these battery cells is Figures 5A-5D The double-layer anode containing plasticizer and thickener is shown as a solid circle (●), while the double-layer anode without plasticizer and thickener is shown as a hollow circle (○). The battery cell with a high concentration of styrene-based thermoplastic, plasticizer and thickener at the interface of the separator has better capacity retention than the battery cell containing a double-layer anode with only styrene-based thermoplastic.

[0255] Example 4: Three-layer anode cycle data

[0256] Electrochemical cells containing the three-layer anodes of the present disclosure were fabricated. The composition of the anode layer of each cell is provided in Table 4. All percentages are by weight.

[0257] Table 4:

[0258]

[0259] Figures 6A-6D Cycling data for each cell in the battery cell is shown. The data for cells 1 and 2 are shown as solid circles (●), and the data for cells 3 and 4 are shown as hollow circles (○). The battery cells were cycled at 45°C, 300psi stack pressure, and a voltage window of 2.5-4.2V. For the first 3 cycles, the battery cells were charged for more than 10 hours and discharged for more than 10 hours, and then for the remaining cycles, charged for more than 5 hours, and discharged for more than 5 hours. The data shows that the discharge capacity decays faster in the battery cell containing the three-layer anode; however, the discharge resistance of the battery cell containing the three-layer anode is significantly lower.

[0260] Example 5: Cycling data of a double-layer anode with a bare current collector

[0261] Electrochemical cells were manufactured comprising a single layer anode comprising 50 wt% silicon and a carbon coated copper current collector. Electrochemical cells comprising a double layer anode were also manufactured. The first layer of the double layer anode (i.e., the layer adjacent to the current collector) comprised 80 wt% silicon. The second layer of the double layer anode comprised 40 wt% silicon. In general, the proportion of silicon in the double layer anode was the same as the proportion of silicon in the single layer anode. These cells had a current collector comprising copper without any coating. The composition of each cell in the cells is shown in Table 5.

[0262] Table 5

[0263]

[0264]

[0265] Figure 7 Cycling data for each cell in the battery cell is shown. The cell was cycled at 45°C, 300 psi stack pressure, and a voltage window of 2.5-4.2 V. For the first 3 cycles, the cell was charged for more than 10 hours and discharged for more than 10 hours, and then charged for more than 5 hours and discharged for more than 5 hours for the remaining cycles. As shown in Figure 7 As seen in Figure 3, the battery cell with a double-layer anode has a more stable battery cell capacity retention after a longer number of cycles compared to the battery cell containing a single-layer anode.

[0266] Without departing from the scope of the present invention, the features described above and the features claimed below can be combined in various ways. Therefore, it should be noted that the content contained in the above description or shown in the accompanying drawings should be interpreted as illustrative rather than restrictive. The above-mentioned embodiments should be considered as examples of the present invention, rather than limiting the scope of the present invention. In addition to the aforementioned embodiments of the present invention, a review of the detailed description and the accompanying drawings will show that there are other embodiments of such inventions. Therefore, many combinations, arrangements, variations and modifications of the aforementioned embodiments of the present invention that are not explicitly set forth herein will still fall within the scope of such inventions. The following claims are intended to cover the general and specific features described herein, as well as all statements of the scope of the method and system of the present invention that can be said to fall therein in language.

Claims

1. An anode composition comprising: a first anode layer, the first anode layer being in operative contact with a second anode layer, the first anode layer and the second anode layer each comprising: an anode active material; and Binder, wherein the second anode layer further comprises a solid electrolyte material, and Wherein the first anode layer optionally comprises a solid electrolyte material.

2. The anode composition of claim 1, wherein the anode active material is present in the first layer in an amount greater than or equal to about 50% by weight of the first layer. 3 . The anode composition of claim 1 , wherein the anode active material is present in the second anode layer in an amount from about 20 wt % to about 50 wt % of the second anode layer. 4 . The anode composition of claim 1 , wherein the anode active material of the first anode layer comprises an inorganic material.

5. The anode composition of claim 4, wherein the inorganic material is selected from the group consisting of silicon, silicon alloys, tin, tin alloys, germanium, germanium alloys, and combinations thereof. The anode composition of claim 5 , wherein the inorganic material is silicon, a silicon alloy, or a combination thereof.

7. The anode composition of claim 1, wherein the first anode layer comprises about 5% or less of a solid electrolyte material.

8. The anode composition of claim 1, wherein the first anode layer comprises about 1% or less of a solid electrolyte material.

9. The anode composition of claim 1, wherein the first anode layer does not include a solid electrolyte material.

10. The anode composition of claim 1, wherein the solid electrolyte material comprises a sulfide-based solid electrolyte material.

11. The anode composition of claim 1, wherein the binder of the first anode layer is different from the binder in the second anode layer. 12 . The anode composition of claim 1 , wherein the binder comprises one or more of styrene-butadiene rubber (SBR), polyvinylidene fluoride (PVdF), carboxymethyl cellulose (CMC), or a combination thereof or a derivative thereof.

13. The anode composition of claim 1, further comprising a current collector in operable contact with the first anode layer.

14. The anode composition of claim 1, wherein the first anode layer or the second anode layer further comprises a carbon-based conductive additive.

15. The anode composition of claim 14, wherein the carbon-based conductive additive is selected from the group consisting of graphite, graphene, carbon black, carbon nanotubes, carbon nanowires, vapor-grown carbon fibers, activated carbon, and combinations thereof.

16. The anode composition of claim 1, wherein the second anode layer further comprises an adhesion promoter.

17. The anode composition of claim 16, wherein the viscosity promoter comprises a hydrocarbon resin.

18. The anode composition of claim 1, wherein the second anode layer further comprises a plasticizer.

19. The anode composition of claim 18, wherein the plasticizer comprises dioctyl phthalate, dibutyl sebacate, mineral oil, or a combination thereof.

20. The anode composition of claim 1 further comprising a third anode layer, the third anode layer comprising Anode active material; Binder; Conductive additives; and solid electrolyte material; and The weight percentage amounts of anode active material, binder, conductive additive and / or solid electrolyte material in the third anode layer are different from those in the first anode layer and the second anode layer.

21. A method for preparing the anode composition according to claim 1, the method comprising: a) forming a first anode layer slurry by: mixing an anode active material, optionally at least one solid electrolyte material, at least one binder material, and a solvent; b) forming a second anode layer slurry by mixing an anode active material, at least one solid electrolyte material, at least one binder material, optionally at least one plasticizer, optionally at least one viscosity enhancer, and a solvent; c) casting the first anode layer slurry onto a substrate; d) casting the second anode layer slurry onto the first anode layer slurry; and e) drying the first anode layer slurry and the second anode layer slurry to form the anode composition.

22. The method of claim 21, wherein the mixing in step a) comprises mixing an anode active material, at least one solid electrolyte material, and at least one binder material, wherein the solid electrolyte material is substantially excluded from the combining.

23. The method of claim 21, wherein the mixing in step a) does not include at least one solid electrolyte material.

24. A method for preparing the anode composition according to claim 1, the method comprising: a) forming a first anode layer slurry by: mixing an anode active material, optionally at least one solid electrolyte material, at least one binder material, and a solvent; b) forming a second anode layer slurry by: mixing an anode active material, at least one solid electrolyte material, at least one binder material, and a solvent; c) casting the first anode layer slurry onto a substrate, and drying the first anode layer slurry; as well as d) casting the second anode layer slurry onto the first anode layer slurry, and drying the second anode layer slurry.

25. A composition comprising a solid double-layer anode, the double-layer anode comprising: A first anode layer, the first anode layer comprising: a first anode active material, wherein the first anode active material is present in the first anode layer in an amount greater than or equal to about 50% by weight of the first anode layer; a first binder; and a first conductive additive; A second anode layer, the second anode layer comprising: a second anode active material, wherein the second anode active material is present in the second anode layer in an amount from about 20% to about 70% by weight of the second anode layer; a second binder; a second conductive additive; as well as Solid electrolyte materials.

26. The composition of claim 25, wherein the first anode layer comprises substantially no solid electrolyte material.

27. The composition of claim 25, wherein the first anode layer is free of solid electrolyte material.

28. The composition of claim 25, wherein the anodically active material is present in the first layer in an amount greater than or equal to about 50% by weight of the first layer.

29. The composition of claim 25, wherein the anode active material is present in the second anode layer in an amount from about 20% to about 50% by weight of the second anode layer.

30. The composition of claim 25, wherein the anode active material of the first anode layer comprises an inorganic material.

31. The composition of claim 30, wherein the inorganic material is selected from the group consisting of silicon, silicon alloys, tin, tin alloys, germanium, germanium alloys, and combinations thereof.

32. The composition of claim 31, wherein the inorganic material is silicon, a silicon alloy, or a combination thereof.

33. The composition of claim 25, wherein the first anode layer comprises about 5% or less solid electrolyte material.

34. The composition of claim 25, wherein the first anode layer comprises about 1% or less of a solid electrolyte material.

35. The composition of claim 25, wherein the solid electrolyte material comprises a sulfide-based solid electrolyte material.

36. The composition of claim 25, wherein the binder of the first anode layer is different from the binder in the second anode layer.

37. The composition of claim 25, wherein the binder comprises one or more of: styrene-butadiene rubber (SBR), polyvinylidene fluoride (PVdF), carboxymethyl cellulose (CMC), or a combination thereof or a derivative thereof.

38. The composition of claim 25, further comprising a current collector in operable contact with the first anode layer.

39. The composition of claim 25, wherein the first anode layer or the second anode layer further comprises a carbon-based conductive additive.

40. The composition of claim 39, wherein the carbon-based conductive additive is selected from the group consisting of graphite, graphene, carbon black, carbon nanotubes, carbon nanowires, vapor grown carbon fibers, activated carbon, and combinations thereof.

41. The composition of claim 25, wherein the second anode layer further comprises an adhesion promoter.

42. The composition of claim 41, wherein the tackifier comprises a hydrocarbon resin.

43. The composition of claim 25, wherein the second anode layer further comprises a plasticizer.

44. The composition of claim 43, wherein the plasticizer comprises dioctyl phthalate, dibutyl sebacate, mineral oil, or a combination thereof.

45. A composition comprising a solid double-layer anode, the double-layer anode comprising: A first anode layer, the first anode layer comprising: a first anode active material, the first anode active material being in an amount of about 60 weight percent or more of the first anode layer; a first solid electrolyte material, the first solid electrolyte material being in an amount of about 20 wt % to about 30 wt % of the first anode layer; and a first binder, the first binder being in an amount of about 0 wt % to about 20 wt % of the first anode layer; as well as A second anode layer, the second anode layer comprising: a second anode active material, the second anode active material being in an amount from about 20 wt % to about 70 wt % of the second anode layer; a second solid electrolyte material, the second solid electrolyte material being in an amount of about 45 weight percent or less of the second anode layer; as well as A second binder, the second binder being in an amount of about 10 weight percent or less of the second anode layer.

46. ​​An electrochemical cell comprising: A double-layer anode, the double-layer anode comprising: a first anode layer, the first anode layer being in operative contact with a second anode layer, the first anode layer and the second anode layer each comprising: an anode active material; and Binder, wherein the second anode layer further comprises a solid electrolyte material, and wherein the first anode layer optionally comprises a solid electrolyte material; The diaphragm layer, and Cathode layer.

47. The electrochemical cell of claim 46, further comprising a first current collector in operable contact with the first anode layer of the bilayer anode.

48. The composition of claim 46, wherein the first anode layer comprises substantially no solid electrolyte material.

49. The composition of claim 46, wherein the first anode layer is free of solid electrolyte material.